Cryo-EM structure of oat amyloid fibrils reveals ordered histidine arrays on the surface - Saiya Li; Shuangjian Li; Qin Cao; Yapeng Fang; Yiping Cao (Food Hydrocolloids, 2027)

An IoT-based intelligent monitoring system for shield tunnels: from multi-source perception to structural response monitoring - Nan Qin; Zhen Liu; Ba Trung Cao; Zili Li; Xian Liu (Tunnelling and Underground Space Technology, 2027)

Real-world impacts of SCR deterioration on NOx emissions from China VI heavy-duty diesel vehicles: Insights from PEMS-based urea mass fraction deterioration tests - Yunpeng Li; Xin Lou; Tao Li; Lanlin Qin; Yingwen Yang; Jinzhu Cao; Dan Zhou; Chaojie Fan; Yong Peng (Fuel, 2026)

Quantitative comparison analysis of coarse-mesh diffusion, pin-by-pin SP3 and pin-by-pin P1 methods for NPP PWR-core multi-cycle simulation by using NECP-Bamboo3.0 - Junwei Qin; Yilin Liang; Yunzhao Li; Liangzhi Cao; Hongchun Wu (Annals of Nuclear Energy, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Photothermal effect derived from confinement of hollow heterogeneous structured Fe2O3@In2S3 for highly efficient solar-driven CO2 reduction - Danyang Li; Huang Qin; Jintao Wen; Mengqing Cao; Dazhao Li; Yalun Wu; Yuanyu Ge; Hai Zhang; Jian Qi; Feifei You (Chemical Engineering Journal, 2026)

A new tetrahydrobenzofuranone and butanoate derivative from the marine-derived fungus Cladosporium sp. GXIMD02111 - Yanlong Li; Xuelian Qin; Quan Teng; Mi Zhou; Pei Cao; Xianqiang Chen (Phytochemistry Letters, 2026)

The acid polysaccharides extracted from Moringa leaf improve DSS-induced ulcerative colitis by targeting intestinal microbiota metabolism - Wen Lang; Xinyun Qin; Yizhe Dou; Keyi Nong; Ruixue Cao; Tingyu Chen; Wanyan Chen; Bin Zhang; Zheng Yang; Bowen Tian; Jijun Wang; Lianbin Li; et al. (Food Research International, 2026)

Bidirectional regulation of heterocyclic amines by flavonoids: insights from flavonoid amination using dihydromyricetin and baicalein - Jingjing Zhang; Hui Cao; Bing Li; Fuying Wang; Qin Duan; Yaru Li; Jinjin Pei; Hui Wang; Juan Carlos Mejuto; Jesús Simal-Gándara; Haolin Zhang (Food Chemistry, 2026)

Development of an ultrasensitive magnetic biosensing platform using SERS and aptamer for the ratio detection of chlorpyrifos in tea - Chenxi Jin; Min Cao; Geqi Li; Jiaqi Wang; Chongyang Qin; Pu Wang; Fei Guo; Dejiang Ni; Zhi Yu; De Zhang; Pei Liang (Food Chemistry, 2026)

From diversity to stability: Acidification, antagonism, and resistance driven by Acetilactobacillus jinshanensis during jiang-flavor baijiu fermentation - Liangqiang Chen; Guozheng Wang; Zhihui Hu; Mengjing Teng; Qingqing Cao; Xing Qin; Hai Du; Fan Yang; Huabin Tu; Li Wang (Food Microbiology, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Discriminating global ore deposit genetic types using chalcopyrite trace elements: Insights from interpretable machine learning - Hong-Kai Li; Ming-Yu Cao; Ben Qin; Peng-Fei Wang; Le Wang (Chemical Geology, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Mechanism of flavor deterioration driven by lipid metabolism in stored barley - Qin Shen; Piao Pan; Lele Lu; Dongmei Cao; Zhijiang Li (Journal of Stored Products Research, 2026)

Potential of RNAi targeting β-N-acetylglucosaminidase(NAG1)for controlling Dendroctonus valens LeConte (Coleoptera: Scolytidae) - Yue Sun; Qin Cao; Yong-Hao Nan; Yang-Nan Hou; Chun-Fang Qi; Ji-Gang Li; Jian-Rong Wei (Journal of Asia-Pacific Entomology, 2026)

Hypoxia-induced downregulation of cAMP drives Ganoderic acid biosynthesis and restricts biofilm development in Ganoderma lucidum - Siyi Wang; Li Tian; Faqin Li; Qin Wang; Yanan Tan; Yanda Ning; Xuewei Cao; Yueqian Liu; Jiaolei Shangguan; Huihui Li; Ailiang Jiang; Mingwen Zhao; et al. (Food Research International, 2026)

Effect of electrohydrodynamic drying on the drying characteristics and nutritional quality of lettuce - Xueru Zhu; Zhiqing Song; Bufan Li; Wenjie Cao; Liqiang Liu; Changjiang Ding; Chunxu Qin (Food Control, 2026)

The TLR9/NF-κB and cGAS/STING pathways mediate​ the assembly of the NLRP3 inflammasome induced by Singapore grouper iridovirus DNA - Lifang Cao; Lu Yang; Runjian Huang; Dekun Tang; Zihan Li; Yunxiang Jiang; Min Yang; Qiwei Qin; Shina Wei (Fish & Shellfish Immunology, 2026)

CXCL8 is associated with aflatoxin B1–triggered injury and caspase-3 activation in porcine kidney epithelial PK15 cells: integrated transcriptomics and CRISPR/Cas9 knockout - Jianlin Yuan; Yuhan Ma; Jinfeng Li; Xizhu Chen; Yiping Wen; Rui Wu; Xinfeng Hang; Heng Huang; Senyan Du; Yiping Wang; Qi-Gui Yan; Xiaobo Huang; et al. (Food and Chemical Toxicology, 2026)

Engineering acid-tolerant RuO2 through dual modulation of d-band center and local proton environment for stable oxygen evolution reaction - Yin Qin; Tiaohao Su; Lingbo Mao; Yanchen Liu; Longhu Cao; Kaikai Li; Tong-Yi Zhang (Chemical Engineering Journal, 2026)

Alginate-based all-biomass photothermal evaporators incorporating hair waste for efficient seawater desalination and wastewater treatment - Zhuofan Wang; Haoran Zhang; Xiaole Gong; Mengyu Cao; Jijie Li; Kaibin Chu; Jingjing Qin; Jingquan Liu (Chemical Engineering Journal, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Gut dysbiosis and Escherichia coli-associated enrichment of antibiotic resistance genes in diarrheal yak calves - Ze Cao; Huanyu Gong; Huilin Qin; Ting Wei; Xiaoqiang He; Kairi Yang; Xiaowei Li; Yanwen Wang; Yunqiang Jia; Xi Lan; Wen He; Xiaoping Jing; et al. (Journal of Hazardous Materials, 2026)

Highly selective transformation of inorganic nitrogen ions to N2 by nZVI-LDH@Biochar: Performance, mechanism and pathway - Yiming Xie; Guangzhu Cao; Ronggao Qin; Yi Qiang; Jingkun Bao; Guanlan Wu; Jinsheng Wang; Ming Li; How Yong Ng (Journal of Environmental Chemical Engineering, 2026)

Self-assembly-confined upconversion photogelation enables centimeter-deep curing for rapid deep-organ hemostasis with sustained pain modulation - Qian Chen; Hongyu Wen; Peng Zhang; Xuhui Xu; Hanying Wang; Guizhu Feng; Qiqi Pei; Li Tian; Yuanyuan Cao; Hongwei Qin; Fusheng Luo; Zhaowei Teng; et al. (Chemical Engineering Journal, 2026)

Defect engineering in conductive MOFs: A strategy for high-performance paraquat electrochemical sensing - Xiao-Qin Li; Hao Ma; Deng-Yue Ma; Tiao-Bin Zhao; Lin-An Cao (Chemical Engineering Journal, 2026)

Dual-nitrogen coordination engineering enables porous carbon-confined Pt-FeN4 atomic interfaces for durable, low-Pt PEM fuel cells - Xiaoqian Xu; Nengneng Xu; Qin Cao; Yuheng Guo; Meng Li; Yuhao Liu; Yawei Li; Guicheng Liu; Woochul Yang; Jong Min Kim; Momo Safari; Jinli Qiao (Chemical Engineering Journal, 2026)

An LC-MS–guided AI enabled serum molecule-interpretable SERS platform for exploratory metabolomic analysis in Alzheimer's disease - Yanling Wang; Chi Zhang; Tong Liu; Qingsong Li; Xue Guan; Yutian Hu; Bo Cao; Xiaohong Wu; Qin Zhou; Feiyun Cui (Analytica Chimica Acta, 2026)

Neural activation patterns underlying football decision-making: evidence for the neural proficiency hypothesis - Ju Li; Yaping Cao; ZhongCheng Li; Xudong Zhao; Zhe Qin; Minghao Huang; Jian Lang; Xiaopeng Chi (Brain Imaging and Behavior, 2026)

Enterococcus faecalis NBRC 100481 Protects the Intestinal Barrier via α-catenin/HMP-1 in Caenorhabditis elegans - Ruina Xu; Jingrui Luo; Chang Huang; Suxiang Li; Chunyan Wu; Qiao Qin; Yong Cao; Yunjiao Chen (Probiotics and Antimicrobial Proteins, 2026)

Multi-marker UPLC-MS/MS detection of sesame, soybean, and peanut oil adulteration in camellia and olive oils: a high-sensitivity approach for food authenticity - Nan Deng; Hui Wang; Fangping Yin; Xiaobo Hu; Jijun Qin; Feifei Zhong; Ben Li; Wenting Cao; Peng Zhou (Food Chemistry, 2026)

A comprehensive review of blue, green, and grey space studies for improving urban microclimate - Xuelin Zhang; Qiusheng Li; Benshuo Wang; Xingyu Qian; Wenbing Liu; Yaojia Guo; Zhen Wu; Ziyong Cao; Chichuan Qin; Jiaru Zhai; Bin Lu (Building and Environment, 2026)

Mitophagy activation for jawbone radiation injury therapy via angiogenesis/osteogenesis-active nanozymes - Tianxiao Wang; Weihua Shao; Ting Zhou; Yuchao Li; Ran Qin; Ziyu Chen; Jikang Cao; Xinyu Hu; Jingxuan Cang; Chang Sun; Yuli Wang; Huijun Jiang; et al. (Science China Life Sciences, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Urban Cooling Island Dynamics During the Development of an Ecological Urban Agglomeration in China - Ziwu Pan; Zunyi Xie; Lifei Huang; Fen Qin; Minmin Yu; Shuyu Yang; Zihan Wang; Jinyuan Han; Zenyan Wang; Yanping Cao; Zhihua Shi; Cangyu Li (Chinese Geographical Science, 2026)

A new amide alkaloid from the coculture liquid cultures of two grape endophytic fungi Penicillium sp. YPT103-2 and Penicillium sp. YPT104 - Yu-Qin Yang; Jin-Feng Cao; Juan-Juan Pu; Dong-Ping Li; Chuan-Mao Zhang; Zhi-Jian Wu; Jian-Hai Ding (Natural Product Research, 2026)

Spatiotemporal decoupling of littoral and lacustrine geosmin dynamics: Implications for early warning in drinking water reservoirs - Yuying Gui; Tengxin Cao; Jie Yang; Jihui Qin; Ming Su; Ziyi Yang; Qi Zhang; Yufan Ai; Jiao Fang; Yingjie Li; Yuanhong Xiao; Zhixiang Hao; et al. (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Mechanism elucidation for electrochemical simultaneous detection of multiple electron-rich phytohormones on a portable flexible sensor and virtual visualization - Shiyu Hu; Xiaoli Wang; Fengwei Li; Shumo Zhou; Xiyi Tang; Yi Peng; Le Wu; Qinyi Cao; Shiyi Xia; Yahui Huang; Songbai Zhang; Jifei Yang; et al. (Journal of Hazardous Materials, 2026)

Corrigendum to “Dynamics of engineered nanomaterials in the rhizosphere: Bidirectional feedback orchestrating multiscale responses” [J. Environ. Chem. Eng. 14 (2026) 121159] - Weicheng Cao; Meng Qin; Yiting Wu; Qingyan Yu; Zhangchunzi Zhao; Xiaodong Nie; Zhongwu Li (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into Cd resilience enhancement by molybdenum trioxide nanoparticles in Solanum nigrum L.: Distinct molecular regulation from Mo6+ through multi-omics perspective - Meng Qin; Jilai Gong; Guangming Zeng; Biao Song; Weicheng Cao; Hongjiao Li; Fuhang Xu (Journal of Environmental Sciences, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

Quartz compositions decipher the source and magmatic-hydrothermal evolution of Himalayan LCT-type pegmatites - Yong-Neng Zhao; Jun-Xing Zhao; Noreen J. Evans; Chang-Tong He; Rui-Zhe Shi; Shen Gao; Li-Qun Zhu; Ke-Zhang Qin; Ming-Jian Cao (Mineralium Deposita, 2026)

Imbalanced Si:N Alters Lipid Production and Photosynthesis in the Marine Diatom Phaeodactylum tricornutum and Dinoflagellate Prorocentrum donghaiense - Jiaxuan Cui; Chuanli Zhang; Rong Bi; Yunyun Zhuang; Xiaoqian Pan; Xiao Qin; Zhong Cao; Hailong Zhang; Li Li; Yang Ding; Meixun Zhao (Journal of Ocean University of China, 2026)

Modeling and simulation of heavy reflector PWR-Core using the NECP-Bamboo software - Junwei Qin; Yunzhao Li; Liangzhi Cao; Hongchun Wu (Annals of Nuclear Energy, 2026)

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Summer carbon-flow characteristics of a marine ranching ecosystem revealed by Ecopath and stable isotopes: A case study from the Bohai Sea, China - Futang Ma; Jianguang Qin; Yingkun Cao; Juan Pan; Bin Wen; Jiamin Sun; Dapeng Liu; Lixin Gong; Gang Wang; Huixin Liu; Qian Li; Jiale Yan; et al. (Marine Pollution Bulletin, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

Structural optimization and experimental measurement of ducted propellers - Zhenqi Li; Xiaojian Cao; Hongde Qin; Chunsheng Yin; Shengyuan Xu (Ocean Engineering, 2026)

Integrating ZSM-5 catalyst with controllable crystal size on macroporous biomass platform for benzene methylation with CO2/H2 - Weichao Qin; Caiyan Li; Tingjun Fu; Ruiwen Cao; Xueqing Wu; Yuyu Liu; Fanhui Meng; Guowu Zhan; Zhong Li (Fuel, 2026)

Color-tunable, time-dependent afterglow polymers from radical copolymerization: Toward multilevel encryption and dynamic anti-counterfeiting - Sicheng Cao; Qin Wu; Shihao Zhang; Yulu Hong; Li-Juan Fan (Chemical Engineering Journal, 2026)

Correction: Water-soluble platinum(II)-porphyrin based on oxygen response for cell hypoxia imaging - Meng-Yan Chai; Yu-Li Dang; He Qin; Li-Xia Xie; Xin Zheng; Lijie Liu; Guoxing Liu; Yu-Qiang Xiang; Cao-Yuan Niu; Sheng-Qiang Guo (Molecular Diversity, 2026)

Cissatriterpenoids D-L, nine undescribed polyhydroxylated oleanane triterpenoids from Cissampelos pareira var. hirsuta - Shuang-Qin Cao; Ru-Yi Pan; Tong-Tong Zhang; Jian-Hong Gong; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Xiao-Ke Zheng; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry, 2026)

Efficient pollutant removal by iron-carbon bioretention system in long-term operation: Stability and performance - Zhou Jianqiang; Song Xichen; Wang Xiaojuan; He Jiangtao; Zhou Yawen; Qin Jie; Xiao Yifei; Gao Suxia; Li Hua; Liu Jianlin; Li Wei; Cao Lianbao; et al. (Journal of Environmental Chemical Engineering, 2026)

Dynamics of engineered nanomaterials in the rhizosphere: Bidirectional feedback orchestrating multiscale responses - Weicheng Cao; Meng Qin; Yiting Wu; Qingyan Yu; Zhangchunzi Zhao; Xiaodong Nie; Zhongwu Li (Journal of Environmental Chemical Engineering, 2026)

Synergistic interactions between gut microbiota and its associated microbial metabolites in Hermetia illucens mediate the reduction of hexavalent chromium - Qingcheng Cao; Yun Li; Cuncheng Liu; Li Chen; Yuanhang Qin; Tielin Wang; Cunwen Wang (Journal of Environmental Sciences, 2026)

Development and validation of a biomimetic mastication simulator for dynamic texture evaluation for cooked rice - Yanyun Cao; Shixin Cai; Xianlian Li; Zihan Qin; Yumei Qin; Yuezhong Mao; Shuangni Shi; Suyun Zhang; Yong Cheng; Shiyi Tian (Food Research International, 2026)

The progress of multiphysics field coupling research on petal-shaped fuel rod - Binxian He; Shusong Qin; Zequan Huang; Jinyi Cao; Wenchao Zhang; Jianchuang Sun; Jincheng Wang; Lipeng Du; Qian Li; Weihua Cai (Annals of Nuclear Energy, 2026)

Quantitative identification of the impact of human activities and climate change on sediment load in the Yellow River Basin of China - Chaomei Wang; Baofu Li; Tao Pan; Yanfeng Chen; Zhaodan Cao; Yanhua Qin; Fan Yang (Environmental Monitoring and Assessment, 2026)

Zinc intoxication triggers ferroptosis in Cryptocaryon irritans tomonts through mitochondrial damage and lipid peroxidation - Zhi Luo; Baotun Wang; Jingyu Zhuang; Hebing Wang; Zhicheng Li; Jizhen Cao; Qin Han; Chuanfu Dong; Anxing Li (Aquaculture, 2026)

Spatial-adaptive active learning identifies ultra-durable and highly active catalysts for acidic oxygen evolution reaction - Bin Cao; Yin Qin; Yan Luo; Zhehan Ying; Zilin Yan; Lu-Tao Weng; Kaikai Li; Tong-Yi Zhang (Science Bulletin, 2026)

A novel land surface temperature retrieval method using channel correlation for atmospheric parameter modeling from SDGSAT-1 data - Li-Qin Cao; Hang Zhao; Du Wang; Yan-Fei Zhong; Fa-Wang Ye (Remote Sensing of Environment, 2026)

Elucidation of dynamic evolution patterns of non-volatile and volatile compounds in peel of Citrus reticulata cv. Chachiensis with different tree ages: a metabolomics-based analysis - Kexin Cao; Chun Yao; Jian Xiao; Rongshao Huang; Zutian Qin; Yusheng Shi; Jianhua Chen; Liangbo Li (Food Research International, 2026)

Advances and challenges in multidimensional architectural applications of 1D/2D/3D convolutional neural networks in food quality assessment - Wenxuan Deng; Qian Qin; Jing Zhao; Yue Yu; Yue Huang; Hao Dong; Fuliang Cao; Zhanming Li (Food Chemistry, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Self-assembled intestinal-targeted nanospheres composite carriers for 2-hydroxychalcone delivery to treat Citrobacter rodentium induced colitis - Xiaoli Qin; Boya Li; Xinjun Qiu; Kai Zhao; Wenjing Niu; Fuyu Yang; Binghai Cao; Huawei Su; Yang He (Chemical Engineering Journal, 2026)

Multi-objective Optimization of Sponge City Storage Tank Considering Inlet and Outlet Water Conditions-based on NSGA-II Algorithm - Wang Xiaojuan; Ma Yingqiang; Li Hao; Qin Jie; Xiao Yifei; Yan Yaping; Zhang Tingting; Gao Suxia; Li Jiapeng; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Water Resources Management, 2026)

Decoding Plant Growth-Promoting Rhizobacteria Volatile Organic Compounds Mediated Growth Promotion in Malus domestica - Nan Zeng; Dandan Wang; Jiahe Pang; Xin Yu Zhao; Chunji Li; Dingcun Zhang; Junliang Ge; Die Zhao; Rutao Gai; Ziqi Cao; Xinyue Bi; Ning Zhang; et al. (Journal of Plant Growth Regulation, 2026)

Global, regional, and national burden of hepatocellular carcinoma and contribution of nine modifiable risk factors across 185 countries/territories in 2022 - Ping Li; Zhan Ding; Yuqi Feng; Xiangyu Ren; Yongyue Wei; Changfa Xia; Yitao Yang; Quanbo Yang; Zhe Wang; Xuehong Zhang; L.G. van der Geest; Herbert Yu; et al. (Science Bulletin, 2026)

Trace element geochemistry of magnetite and hematite from the Jinchang porphyry Au-Cu deposit, northeast China: Implications for fluid evolution and cobalt enrichment - Peng-Fei Shan; Ming-Jian Cao; Noreen J. Evans; Le Wang; Yi Li; Yu-Suo Zhao; Ke-Zhang Qin (Journal of Asian Earth Sciences, 2026)

Numerical investigation on the influence of temperature on combustion and emission characteristics of NH3/H2/CH4 mixtures under gas turbine conditions - Yanfei Zhang; Qing Hao; Mingming Huang; Zhenxian Liu; Qin Li; Zewen Yu; Jianfang Du; Xiao Zhang; Zhuoming Xiong; Qingkui Zhang; Yumeng Cao; Haoxi Sha (Fuel, 2026)

Crosslinked polymer aerogel with multiple binding sites for efficient uranium separation from uranium-containing wastewater - Yaping Jian; Jiacheng Zhang; Xuewen Cao; Jipeng Li; Qin Peng; Xuefeng Tian; Jianfei Du; Yihui Yuan; Ning Wang (Environmental Research, 2026)

Can urinary OH-PAHs serve as biomarkers for indicating inhalation exposure to PAHs of children: Evidence based on a panel study - Wenjing Zhao; Jiajun He; Zhangning Li; Huanming Li; Xiaojie Zhou; Sreynith Lis; Xinyi Wang; Suzhen Cao; Beibei Wang; Xiaoli Duan; Ning Qin (Environmental Pollution, 2026)

Water-soluble platinum(II)-porphyrin based on oxygen response for cell hypoxia imaging - Meng-Yan Chai; Yu-Li Dang; He Qin; Li-Xia Xie; Xin Zheng; Lijie Liu; Guoxing Liu; Yu-Qiang Xiang; Cao-Yuan Niu; Sheng-Qiang Guo (Molecular Diversity, 2026)

Genetic characteristics of three duck-original H1N1 influenza A viruses isolated in China - Qiuqi Kan; Xuefeng Yin; Xingyao Guo; Xinran Chu; Jianjun Sang; Xudong Cao; Jixiang Wang; Wenjie Jiang; Zhehong Zhao; Quan Xie; Tuofan Li; Hongxia Shao; et al. (Veterinary Microbiology, 2026)

Attenuation and disturbances of surface and coal seam seismic waves caused by ground deep-hole blasting - Xianxi Bai; Anye Cao; Xueqi Zhang; Xufeng Qin; Yingshi Gu; Geng Li; Chengchun Xue; Yingyuan Wen (Soil Dynamics and Earthquake Engineering, 2026)

Analysis of hydrodynamic and motion performance of toroidal propeller - Diver propulsion vehicle - Zhenqi Li; Xiaojian Cao; Hongde Qin; Chunsheng Yin; Shengyuan Xu (Ocean Engineering, 2026)

Cobalt-Te-Au occurrence, genesis, and metallogenic potential of the Jiama skarn orebody, Tibet, China - Shuo Wang; MingJian Cao; DongMei Tang; Noreen J. Evans; GuangMing Li; Wangdui Silang; KeZhang Qin (Journal of Asian Earth Sciences, 2026)

Toward noise-resilient retrieval of land surface temperature and emissivity using airborne thermal infrared hyperspectral imagery - Du Wang; Li-Qin Cao; Yu-Hao Du; Hai-Yang Xiong; Fa-Wang Ye; Yan-Fei Zhong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Preliminary application of synchrotron time-resolved SAXS in in-situ study of dust explosion - Haijuan Wu; Jiahao Liu; Xiaolan Ji; Wenmin Li; Longlong Yang; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Xiong Cao; Yixin Zhao (Fuel, 2026)

Dual driven effect of Znδ+ sites in the oxide-zeolite catalyst for benzene alkylation coupled with CO2 hydrogenation - Ruiwen Cao; Tingjun Fu; Yuhang Guo; Weichao Qin; Zhong Li (Chemical Engineering Journal, 2026)

Dual-Excitation Ratiometric Fluorescent Probe for Identification of Biogenic Amines and Its Application in Food Spoilage Detection - Chen Li; Shengjie Niu; Siwen Yu; Hang Li; Shengrui Zhang; Xiaoyan Cao; Lihua Li; Huiping Dai; Jiangjiang Sun; Hua Li; Qin Wang (Journal of Fluorescence, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Spatiotemporal variations in global lake clarity and responses to climate and landscape drivers - Yibo Zhang; Yunlin Zhang; R. Iestyn Woolway; Zhigang Cao; Xiwen Wang; Jian Zhou; Yongqiang Zhou; Weijia Wang; Na Li; Boqiang Qin; Kun Shi (Science Bulletin, 2025)

Improving runoff simulation in cold alpine regions based on VIC-glacier by combining LSTM error correction technology - Chen Shi; Qin Liu; Yungang Bai; Qiying Yu; Zhenlin Lu; Chengshuai Liu; Biao Cao; Lei Ren; Ming Li; Gan Miao; Caihong Hu (Journal of Hydrology, 2025)

Temporal variation in soil detachment capacity of high-severity post-fire in dry-warm valley forest lands in Southwest China - Xiaosong Qin; Yi Wang; Longxi Cao; Wei He; Yongkang Li; Dongdong Hou; Yufan Wang; Jia Xu (Journal of Hydrology, 2025)

Dual roles of atrazine as an organic contaminant and indicator of intermediate oxidants during sulfite activation of permanganate - Qin Guo; Ying Cao; Jin Jiang; Juan Li (Journal of Environmental Chemical Engineering, 2025)

Dynamic DIA proteomics of mare's milk reveals distinct colostrum signatures and stage-specific lactation profiles - Luan Yue; Wendan Tang; Cao Li; Xiaoyu Yue; Xiaoyun He; Aleksandr Mikhailovich Zaitsev; Mu Zhang; Valery Vasilievich Kalaschnikov; Jingyi Li; Qin Wang (Food Chemistry, 2025)

Impact of esterification degree of pectic polysaccharides from quinoa microgreen on protective effects against dextran sulfate sodium-induced colitis in mice - Wang Guo; Bo Li; Mao-Qing Wang; Yang Cao; Qin Yuan; Wen Liu; Yi-Chen Hu; Liang Zou; Shengpeng Wang; Ding-Tao Wu (Food Bioscience, 2025)

Scenario-driven modeling of mountain ecosystems: land use-carbon dynamics simulation based on the coupled SD-FLUS-InVEST framework - Qin Yaowei; Yan Yu; Dong Jiaqi; Zhao Zhenyu; Li Shuangjiang; Cao Jiansheng; Xiao Jieying (Ecological Modelling, 2025)

Effects of Duckweed Species Diversity on Physiological Responses and Removal Efficiency under Cadmium Stress - Qin Cao; Ai-Juan Tan; Yan Lan; Wen-Bo Zou; Gui-Li Yang (Water, Air, & Soil Pollution, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Characterization of 4-coumarate CoA ligase (4CL) gene family and functional study of Sm4CL2/3/7/9 in Salvia miltiorrhiza - Fan Fu; Huiting Qin; Yujie Xin; Qianmo Li; Heng Kang; Limin Han; Wenping Hua; Xiaoyan Cao (Functional & Integrative Genomics, 2025)

Astragaloside IV protects against high altitude hypoxia-induced cardiac injury through the CaSR-NF-kB and EGFR-PI3K-AKT-MDM2 pathways - Xiaowen Li; Ruiqi Cao; Ling Zhang; Jie Chen; Zhen Qin; Danyi Huang; Yazhen Nie; Zheng Duan; Lingling Pu; Zirou Wang; Ran Li; Xinxing Wang; et al. (Apoptosis, 2025)

Investigation of the Alterations in the Gut Microbiota and Intestinal Mucosa in Mice Infected with Echinococcus multilocularis - Deping Cao; Wenjun Huang; Mingquan Pang; Jiajing Li; Haitao Huang; Hui Ma; Dayu Li; Yufei Qin; Xiaohong Peng; Haining Fan (Acta Parasitologica, 2025)

Research on the Reinforcement Effect of the Elephant-Foot Method in Aeolian Sand Tunnels - Ji-hua Qin; Xi-peng Li; Ya Wang; Xiao-li Cao; Dong Li; Yi-guo Xue; Fan-meng Kong; Hui-min Gong; Bang-xiang Li; Chao Lu; Guang-kun Li (Applied Geophysics, 2025)

Cryoprotective activity of different characterized fractions isolated from sea cucumber intestinal protein hydrolysates against salmon - Zhe Xu; Shuang Guan; ShengAo Cao; Rui Zhang; Hanxiong Liu; Zijin Qin; Xiufang Dong; Jianping Wu; Tingting Li (Food Chemistry, 2025)

Synergistic multi-sites single-atom catalysts enabling ultrastable zinc-air batteries via cascading H2O2 suppression and corrosion resistance - Heng Zhang; Huijuan Yang; Kang Yu; Xuhong Yan; Yifan Li; Yuanjie Yi; Jian Qin; Wei Xiao; Guiqiang Cao; Ruixain Duan; Yangyang Luo; Huaming Qian; et al. (Chemical Engineering Journal, 2025)

High-severity fire reduces soil erosion resistance: A study based on 4-year field monitoring data in dry-warm valley in Southwest China - Xiaosong Qin; Yi Wang; Longxi Cao; Ping Ren; Wei He; Yongkang Li; Dongdong Hou; Yufan Wang; Jia Xu (CATENA, 2025)

Vertical flow structures in a finite patch of natural submerged vegetation under wave-current conditions: Laboratory experiments - Jiadong Fan; Cuiping Kuang; Hongyi Li; Xin Cong; Deping Cao; Rufu Qin (Journal of Hydrology, 2025)

Longhua, the first five-element (Ni-Co-As-Ag-Bi) hydrothermal vein deposit in China: Constraints from mineral characteristics and fluid evolution - Xinshuo Huang; Mingjian Cao; Baolin Zhang; Noreen J. Evans; Zengsheng Li; Xinyu Zou; Shuo Wang; Pengfei Shan; Junyu Li; Guangming Li; Kezhang Qin (Journal of Asian Earth Sciences, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Mitochondrial DNA leakage and micronucleus formation activate the cGAS–STING pathway in aristolochic acid I-induced nephritis - Yu yang Lei; Yu shi Hu; Yi yi Cao; Jing Xi; Yu ning Ma; Xiao hong Zhang; Qin wen Gao; Ji an Fu; Xin yu Zhang; Li Su; Yang Luan (Food and Chemical Toxicology, 2025)

Role of low-dose cadmium exposure to the pathogenesis of gestational diabetes mellitus - Huan Chen; Jinlian Bin; Zhongqiang Cao; Yidan Luo; Pengshu Song; Jiajia He; Shi Lu; Gaga Mahai; Jianqiu Zheng; Yuanyuan Li; Jie Qin (Environmental Pollution, 2025)

Antimony nanoparticles embedded in dense porous carbon microspheres for advanced sodium-ion batteries with superior volumetric capacity - Laifen Qin; Chuanyang Xiao; Zhijian Dang; Hailiang Cao; Liang Meng; Wei Deng; Longtao Li; Zhi Zheng; Junjie Guo (Chemical Engineering Journal, 2025)

Sediment redox state threshold for N2O emissions and indirect regulatory impact of organic carbon in shallow lakes - Hui Li; Huatang Deng; Yingying Cai; Jianfen Li; Zhenhua Qin; Fangyuan Chen; Xiuyun Cao; Chunlei Song; XinBin Duan (Journal of Soils and Sediments, 2025)

Land surface temperatures outperform gridded air temperatures in modeling forest growth across the Northern Hemisphere - Feiyu Yang; Yujiu Xiong; Wenjin Wang; Hongxing Hu; Mantik Lai; Chao Zhang; Jiahao Cao; Leyao Zhu; Qibo Fan; Ying Zhao; Zhou Wang; Yaling Zhang; et al. (Agricultural and Forest Meteorology, 2025)

A review of organic additives in CMP slurry - Jiaqi Fu; Zuozuo Wu; Yiting Li; Daming Wang; Wuju Qin; Yangjian Li; Shuai Yuan; Jianwei Cao; Deren Yang (Next Research, 2025)

Biochar-composting facilitates hexavalent chromium reduction and improves soil quality and microbial community structure - Guangpeng Pei; Jiarui Cao; Zhenye Tong; Rui Wang; Yuxin Li; Xuwei Li; Junmei Qin; Fenwu Liu (Journal of Environmental Management, 2025)

Dry reforming of methane by La2NiO4 perovskite oxide: Cordierite-ceramic-supporting monolithic catalyst with Cu B-site substitution improving reacting performance - Dingshan Cao; Zhen Qin; Cong Luo; Xiaoshan Li; Zhaowei Shi; Fan Wu; Ying Zheng; Liqi Zhang (Chemical Engineering Journal, 2025)

Mechano-kinetic integrated carbon coating enables fast-charging micro‑silicon anodes - Junwei Han; Xin Qin; Qian Xu; Lu Zhao; Debin Kong; Yun Cao; Fei Yang; Xia Hu; Yafei Wang; Mingxue Zuo; Huiyu Yu; Bocheng Yang; et al. (Chemical Engineering Journal, 2025)

Incorporation of straw from maize and early rice differentiated sequestration and stability of soil organic carbon–A long-term field incubation of 13C-labelled straw under maize -rice and double rice cropping - Ming Zhan; Mingguang Qin; Xuedong Fang; Moussa Traore; Yingjian Cao; Chengfang Li (Plant and Soil, 2025)

Wood-inspired N, P-codoped hierarchically porous carbon aerogels decorated with Co3O4 nanoparticles for fast and sustainable emerging organic contaminants degradation - Junqi Liao; Shuqi Cao; Meng Qin; Yinliang Zhang; Yulan Lu; Liping Li; Chuigen Guo; Zhinan Wang (Journal of Cleaner Production, 2025)

Enhanced recycling and utilization of industrial waste gas H2S through photoelectrochemical methods with ZnFe2O4/ZnIn2S4 heterojunction containing NiCoP co-catalyst - Zhichao Hao; Xu Sun; Lifeng Zhang; Ruikai Wang; Haiyan Li; Junjie Qin; Chenghui Xia; Bohua Dong; Lixin Cao (Chemical Engineering Journal, 2025)

Experimental Study on Mechanical Integrity of Cement and EICP-Solidified Soil for Scour Protection of Pile Foundations - Feng Cao; Qilin Zhang; Wei Qin; Haoran Ouyang; Zhiyue Li; Yutao Peng; Guoliang Dai (Journal of Marine Science and Engineering, 2025)
Among the scour protection measures for pile foundations, the use of solidified mud has demonstrated effective protection against scour. However, research on the mechanical integrity of this protective measure is relatively scarce. Therefore, a series of experiments were performed on cement-solidified soil and Enzyme-Induced Carbonate Precipitation (ECIP) solidified soil to analyze fluidity, disintegration, and unconfined compressive strength, along with an analysis of influencing parameters. Test results show the following: for cement-solidified soil, fluidity decreases with higher cement content, while its disintegration rate decreases with more cement and its unconfined compressive strength increases with a longer curing time and higher cement content. For ECIP-solidified soil, fluidity decreases with higher soy powder concentration but increases with higher binder solution concentration. ECIP’s initial disintegration rate increases with binder concentration, but after 7 days curing, its disintegration rate decreases with both higher binder concentration and higher soy powder concentration. ECIP’s strength increases with higher soy powder concentration. Crucially, both types of solidified soil exhibit decreased unconfined compressive strength with higher initial water content. The research results can provide a reference for the construction of solidified soil in the field of scour protection.

Insight into ion-induced stability degradation in all-perovskite tandem photovoltaics: quantitative characterization and effective manipulation strategies - Yining Bao; Tianshu Ma; Yuqi Zhang; Luolei Shi; Linling Qin; Changlei Wang; Guoyang Cao; Xiaofeng Li; Zhenhai Yang (Science Bulletin, 2025)

Joint technique “parallel peptide synthesis & de novo sequencing” development for the structure verification and high-throughput activity screening of biological peptides from sea cucumber (Stichopus japonicus) intestinal hydrolysate - Yimeng Li; Shengfang Gao; Xiaohui Zhang; Zhuo Cao; Youyou Guo; Runkun Zhao; Yonggang Liu; Xinxin Li; Hongying Lin; Qi Qin; Bingqing Yi; Guodong Zhao (Food Research International, 2025)

Decaying logs and gap positions jointly maintain the structure and function of soil invertebrate community in a subalpine forest - Yurui Jiang; Zhuang Wang; Rui Cao; Qin Wang; Weizhong Li; Wanqin Yang (Plant and Soil, 2025)

Study on the early warning index gases of lignocellulosic biomass during the auto-oxidation process - Jinhu Li; Mengru Cai; Qin Cao; Hui Zhuo; Wei Lu; Tenneh Maria Andrews (Process Safety and Environmental Protection, 2025)

Research on the role of bamboo species in the restoration of heavy metal-contaminated soil - Qin Cao; Guang-Qian Gou; Zhao-Xia Dai; Ai-Juan Tan; Gui-Li Yang (Journal of Environmental Management, 2025)

Customized screening of ACE2 regulatory peptides from oyster to mitigate LPS-induced acute lung injury based on SPR technology - Xiaoyu Xia; Caixing Wen; Wenhong Cao; Xiaoming Qin; Yujin Li; Haisheng Lin; Zhongqin Chen; Huina Zheng; Guoping Zhu; Jialong Gao (Food Bioscience, 2025)

Astronomically forcing hydrological controls on salinity variations during the late Ordovician-early Silurian in the Upper Yangtze area: Responses to the monsoon climate and HICE - Min Xiong; Lei Chen; Chongjie Liao; Xin Chen; Xiucheng Tan; Jian Cao; Shuaicai Wu; Hexing Qin; Zuyou Zhang; Gaoxiang Wang; Dazhong Li; Jiaxun Lu (Chemical Geology, 2025)

Preparation of Amino-Functionalized Carbon Microspheres and Their Adsorption Characteristics for Pb2+ in Aqueous Solutions - Jiangfei Cao; Shuqi Xiao; Wenting Deng; Jiaying Zhang; Rui Chen; Jianqiao Qin; Xiang Li (Water, Air, & Soil Pollution, 2025)

Integrative analysis based on CRISPR screen identifies apilimod as a potential therapeutic agent for cisplatin-induced acute kidney injury treatment - Yunpeng Chu; Muyun Wei; Zhongyu Cao; Luan Chen; Jie Tan; Wei Bao; Fan Yang; Yingtian Zhang; Yunxiao Lin; Yutong Zhang; Shiyi Li; Cai Lv; et al. (Science China Life Sciences, 2025)

Foliar application of ferroferric oxide nanomaterials enhance source-sink communication and growth in soybean - Xing Luo; Wen Ao; Yusheng Qin; Chuanxi Wang; Xiaona Li; Le Yue; Yangyang Ma; Xuesong Cao; Zhenyu Wang; Xianzheng Yuan (Journal of Environmental Management, 2025)

Synergistic effect of nutrient starvation and abscisic acid on growth and starch accumulation in duckweed - Qin Cao; Yue-Qi Zhang; Ai-Juan Tan; Zhu Li; Gui-Li Yang (Planta, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Preferred crystal plane growth orientation induced by low-energy ions for highly reversible zinc anodes - Guanzhong Wang; Xiyan Bao; Xiaofang Wang; Xize Chen; Wei Lai; Di Wu; Chen Zhang; Lin Gao; Minglei Cao; Xingxing Li; Qin Wang; Hao Wang; et al. (Chemical Engineering Journal, 2025)

Decrease in urban-rural differences of nighttime humid heatwaves in the Yangtze River Delta, China - Wenqing Zhou; Liping Zhang; Qin Zhang; Yi Li; Gangsheng Wang; Zhenyu Tang; Xiao Li; Zhengfeng Bao; Hui Cao; Benjun Jia (Atmospheric Research, 2025)

P1 generalized equivalence theory for PWR-core pin-by-pin neutronics calculation - Junwei Qin; Yunzhao Li; Liangzhi Cao; Hongchun Wu (Annals of Nuclear Energy, 2025)

Chinese chestnut did not induce negative plant soil feedback during centuries of growth - Xu Cheng; Zhichun Yan; Qian Li; Lucas Schmitz; Jundi Yan; Yueyang Ge; Yanping Lan; Yaceng Zhao; Yiyang Wang; Guangdong Li; Yang Liu; Martinus Schneijderberg; et al. (Science of The Total Environment, 2025)

Angular normalization of GOES-16 and GOES-17 land surface temperature over overlapping region using an extended time-evolving kernel-driven model - Boxiong Qin; Shuisen Chen; Biao Cao; Yunyue Yu; Peng Yu; Qiang Na; Enqing Hou; Dan Li; Kai Jia; Yingpin Yang; Tian Hu; Zunjian Bian; et al. (Remote Sensing of Environment, 2025)

Coral-Symbiodiniaceae symbiotic associations under antibiotic stress: Accumulation patterns and potential physiological effects in a natural reef - Zhicong Yan; Xiaocong Cao; Hao Su; Changqing Li; Jiamin Lin; Kai Tang; Jiahua Zhang; Hangbo Fan; Qin Chen; Jia Tang; Zhi Zhou (Journal of Hazardous Materials, 2025)

Establishing age-group specific reference intervals of human salivary proteome and its preliminary application for epilepsy diagnosis - Nianci Xue; Xia Xia; Yini Wang; Xianju Li; Nairen Zheng; Yi Wang; Baoying Gong; Bin Zhang; Yanjia Chen; Yue Chen; Yanjuan Li; Hong Cao; et al. (Science China Life Sciences, 2025)

Effect of Interaction of ATG7 and Plasma Metal Concentrations on Cognitive Impairment in Rural China - Xu Tang; Jiejing Cao; Jiansheng Cai; Xiaoting Mo; Yanfei Wei; Kailian He; Zeyan Ye; Yu Jian Liang; Linhai Zhao; Lidong Qin; You Li; Jian Qin; et al. (Journal of Molecular Neuroscience, 2025)

Effect of some feed additives on osmoregulation in aquatic animals - Quanquan Cao; Qin Zhang; Shiqi Li; Alkhateib Gaafar; Abdelgayed Metwaly Younes; Khalid Hussain Rind; Haifeng Liu; Jun Jiang (Aquaculture, 2025)

Comparative analysis of Seabuckthorn and its significant component in enhancing fish mucosal immunity - Yuhang Liu; Lian Su; Danying Cao; Nan Wu; Yuhang Hu; Fatima Altaf; Jialin Li; Qingsong Zhu; Junheng Liu; Qianqian Zhang; Haokun Liu; Yingyin Cheng; et al. (Aquaculture, 2025)

Cadmium induces spontaneous abortion by impairing endometrial stromal cell decidualization - Xue-Ke Zhang; Xuan Li; Xing-Xing Han; Dong-Ying Sun; Yu-Qin Wang; Zi-Zhuo Cao; Lu Liu; Zi-Han Meng; Guo-Jing Li; Yu-Jie Dong; Dan-Yang Li; Xiao-Qing Peng; et al. (Toxicology, 2025)

Involvement of inorganic nitrogen species ( NO X − (x = 2, 3)) in the degradation of organic contaminants in environmental waters via UV irradiation or chemical oxidation: A dual-edged approach - Jiebin Duan; Ying Cao; Quanzhen Yang; Wenqi Li; Qianqian Huang; Qin Guo; Jin Jiang (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Total nutritional double emulsion-based supplement enriched with low-molecular-weight oyster peptides: A promising nutritional strategy for alleviating cachexia in chemotherapy-treated Lewis lung cancer mice - Jinzhen Li; Wenhong Cao; Zhongqin Chen; Haisheng Lin; Jialong Gao; Mingtang Tan; Xiaoming Qin; Huina Zheng (Food Bioscience, 2025)

Occurrence, distribution, and dietary risk assessment of pesticides in apples at the provincial scale - Tao Pei; Wei Pan; Jindong Li; Junli Cao; Shu Qin; Li Li (Food Control, 2025)

The metabolic redundancy relieving VFAs shocks in anaerobic digestion system exposed sequentially to increasing acetic acid loading - Qin Cao; Xianghui Meng; Fenglin Jia; Jiabao Li; Xiaofeng Liu; Dong Li (Chemical Engineering Journal, 2025)

Top-to-south shear at the base of the eastern Tethyan Himalayan Sequence during the Eocene-Oligocene Himalayan orogeny - Zhiqin Xu; An Yin; Hua Xiang; Qin Wang; Guangwei Li; Hanwen Dong; Hui Cao; Jianguo Gao (Tectonophysics, 2025)

Production of hydroponic mug bean sprout using microalgae fermentation wastewater and activated carbon pretreatment - Sana Irshad; Asad Nawaz; Xiaofang Luo; Zunhua Li; Meifeng Wang; Linyan Cao; Zhenmin Cao; Zuodong Qin (Journal of Water Process Engineering, 2025)

Cobalt/nitrogen co-doped carbon nanosheets from coal-based graphene quantum dots boosted oxygen reduction - Qin Li; Jing Lei; Xueyang Zhao; Qin Geng; Hongtao Xie; Yizhao Li; Yali Cao (Fuel, 2025)

Screening and characterization of an antifreeze peptide from sea cucumber intestinal protein hydrolysates - Zhe Xu; ShengAo Cao; Na Cui; Rui Zhang; Zijin Qin; Hanxiong Liu; Jianping Wu; Ming Du; Zhijian Tan; Tingting Li (Food Chemistry, 2025)

Single-atom nanozyme immunoassay with electron-rich property for clinical patient cancer detection - Qingshan Liu; Guo Li; Yang Cao; Yaoyao Ren; Qiong Qin; Lei Li; Hao Zhang; Qi Xin; Xiaoqun Gong; Lingyu Zhao; Shu Zhang; Yonghui Li; et al. (Chemical Engineering Journal, 2025)

Mitigating harmful cyanobacterial blooms in drinking water reservoirs through in-situ sediment resuspension - Jiao Fang; Yande Li; Ming Su; Tengxin Cao; Xufeng Sun; Yufan Ai; Jinyi Qin; Jianwei Yu; Min Yang (Water Research, 2024)

A comprehensive genetic variant reference for the Chinese population - Tao Jiang; Hongzhe Guo; Yadong Liu; Gaoyang Li; Zhe Cui; Xinran Cui; Yue Liu; Yang Li; Anqi Zhang; Shuqi Cao; Tianyi Zhao; Liran Juan; et al. (Science Bulletin, 2024)

Airborne thermal infrared hyperspectral image temperature and emissivity retrieval based on inter-channel correlated automatic atmospheric compensation and TES - Du Wang; Li-Qin Cao; Lyu-Zhou Gao; Yan-Fei Zhong (Remote Sensing of Environment, 2024)

Occurrence of per- and polyfluoroalkyl substances in drinking water in China and health risk assessment based on a probabilistic approach - Linqian Li; Suzhen Cao; Xiaochen Shang; Liwen Zhang; Jiacheng Guan; Kan Shao; Ning Qin; Xiaoli Duan (Journal of Hazardous Materials, 2024)

Legume and maize intercropping enhances subsequent oilseed rape productivity and stability under reduced nitrogen input - Lu Yang; Chiming Gu; Wei Huang; Haibin Chang; Yuan Gao; Yinshui Li; Jing Dai; Xiaoyong Li; Wenshi Hu; Weidong Cao; Xing Liao; Lu Qin (Field Crops Research, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Accumulation of Prion Triggers the Enhanced Glycolysis via Activation of AMKP Pathway in Prion-Infected Rodent and Cell Models - Qin Fan; Kang Xiao; Ruhan A; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Chao Hu; Xiao-Xi Jia; Chu-Mou Liu; Xin Liu; Cao Chen; Qi Shi; et al. (Molecular Neurobiology, 2024)

Impacts of urban expansion on air temperature and humidity during 2022 mega-heatwave over the Yangtze River Delta, China - Wenqing Zhou; Liping Zhang; Gangsheng Wang; Qin Zhang; Hui Cao; Hairong Zhang; Benjun Jia; Zhenyu Tang; Xiao Li; Lina Liu (Science of The Total Environment, 2024)

Centrifugation-modulated uniform antibacterial paper with well-interconnected hierarchical pores for flexible high-sensitivity humidity monitoring - Tongtong Qin; Zhengpeng Yang; Huili Fu; Liming Zhao; Zhenzhong Yong; Li Chen; Kunjie Wu; Chenxuan Li; Chunjing Zhang; Yongyi Zhang; Yufang Cao; Hengyi Yu; et al. (Chemical Engineering Journal, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Polymerized lignin based carbon nanofiber for high-performance energy generator and storage - Chuangqi Zheng; Qiping Cao; Lei Pu; Jingyu Xu; Hui Gong; Ziyi Shen; Kaibin Chu; Dechao Chen; Qin Li; Ning Han; Yao Li (Chemical Engineering Journal, 2024)

Nutrient regeneration patterns for initiating and maintaining algae blooms-a case study of in Lake Taihu - Hui Li; Yingying Cai; Huatang Deng; Zhenhua Qin; Jianfen Li; Xiuyun Cao; Yiyong Zhou; Chunlei Song; XinBin Duan (Chemosphere, 2024)

The shifting pattern of CO2 source sink in a subtropical urbanizing lightly eutrophic lake - Rongjie Yang; Huixing Song; Qiao Qin; Yingying Chen; Di Li; Yuling Qiu; Kezhu Lu; Yike Tan; Qingqing Chen; Xinhao Cao; Shiliang Liu (Science of The Total Environment, 2024)

The underlying mechanisms of oxytetracycline degradation mediated by gut microbial proteins and metabolites in Hermetia illucens - Qingcheng Cao; Cuncheng Liu; Yun Li; Yuanhang Qin; Cunwen Wang; Tielin Wang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

Restricted-Enhanced Electrochemiluminescence biosensor of low excitation potential carbon quantum dots driven by magnetic Metal-Organic frameworks for sensitive immunoassay of neuron specific enolase - Jinglong Fang; Min Li; Dongmei Cao; Jingjing Zhang; Huan Wang; Wei Cao; Qin Wei (Chemical Engineering Journal, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Cellulose-based yellow-green emitting carbon dots with large Stokes shift as effective “turn off-on” fluorescence platforms for Cr (VI) and AA dual efficacy detection - Yan-feng Li; Xian Zhang; Qian Lu; Jing-zhen Cao; Sheng Gao; Qin-ze Liu; Xiao-xia Cai; Hui Zhao (Analytica Chimica Acta, 2024)

Nucleophilic hydrolysis of dichloroacetonitrile and trichloroacetonitrile disinfection byproducts by peroxymonosulfate: Kinetics and mechanisms - Yangyi Yu; Juan Li; Junhui Zhou; Ying Cao; Qin Guo; Yongze Liu; Yi Yang; Jin Jiang (Chemosphere, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Electro-mechano transduction of stacked triboelectric nanogenerator considering wave force: Modeling, validation and applications - Chen Cao; Fan Shen; Chuanfu Xin; Qin Zhang; Qiwei Zheng; Ying Gong; Heming Liu; Yan Peng; Zhongjie Li (Chemical Engineering Journal, 2024)

Grassland biomass allocation across continents and grazing practices and its response to climate and altitude - Jianjun Cao; Yumei Li; Asim Biswas; Nicholas M. Holden; Jan F. Adamowski; Fengchu Wang; Shuyan Hong; Yanyan Qin (Agricultural and Forest Meteorology, 2024)

Synergistic impacts of antibiotics and heavy metals on Hermetia illucens: Unveiling dynamics in larval gut bacterial communities and microbial metabolites - Qingcheng Cao; Cuncheng Liu; Li Chen; Yuanhang Qin; Tielin Wang; Cunwen Wang (Journal of Environmental Management, 2024)

Towards long-term, high-accuracy, and continuous satellite total and fine-mode aerosol records: Enhanced Land General Aerosol (e-LaGA) retrieval algorithm for VIIRS - Lunche Wang; Xin Su; Yi Wang; Mengdan Cao; Qin Lang; Huaping Li; Junyao Sun; Ming Zhang; Wenmin Qin; Lei Li; Leiku Yang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Aging- and alcohol-associated spatial transcriptomic signature in mouse acute pancreatitis reveals heterogeneity of inflammation and potential pathogenic factors - Rachel R. Tindall; Yuntao Yang; Isabella Hernandez; Amy Qin; Jiajing Li; Yinjie Zhang; Thomas H. Gomez; Mamoun Younes; Qiang Shen; Jennifer M. Bailey-Lundberg; Zhongming Zhao; Daniel Kraushaar; et al. (Journal of Molecular Medicine, 2024)
The rapidly aging population is consuming more alcohol, leading to increased alcohol-associated acute pancreatitis (AAP) with high mortality. However, the mechanisms remain undefined, and currently there are no effective therapies available. This study aims to elucidate aging- and alcohol-associated spatial transcriptomic signature by establishing an aging AAP mouse model and applying Visium spatial transcriptomics for understanding of the mechanisms in the context of the pancreatic tissue. Upon alcohol diet feeding and caerulein treatment, aging mice (18 months) developed significantly more severe AAP with 5.0-fold increase of injury score and 2.4-fold increase of amylase compared to young mice (3 months). Via Visium spatial transcriptomics, eight distinct tissue clusters were revealed from aggregated transcriptomes of aging and young AAP mice: five acinar, two stromal, and one islet, which were then merged into three clusters: acinar, stromal, and islet for the comparative analysis. Compared to young AAP mice, > 1300 differentially expressed genes (DEGs) and approximately 3000 differentially regulated pathways were identified in aging AAP mice. The top five DEGs upregulated in aging AAP mice include Mmp8 , Ppbp , Serpina3m , Cxcl13 , and Hamp with heterogeneous distributions among the clusters. Taken together, this study demonstrates spatial heterogeneity of inflammatory processes in aging AAP mice, offering novel insights into the mechanisms and potential drivers for AAP development. Key messages Mechanisms regarding high mortality of AAP in aging remain undefined. An aging AAP mouse model was developed recapturing clinical exhibition in humans. Spatial transcriptomics identified contrasted DEGs in aging vs. young AAP mice. Top five DEGs were Mmp8 , Ppbp , Serpina3m , Cxcl13 , and Hamp in aging vs. young AAP mice. Our findings shed insights for identification of molecular drivers in aging AAP.

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Retarding anion migration for alleviating concentration polarization towards stable polymer lithium-metal batteries - Manying Cui; Yanyang Qin; Zhichao Li; Hongyang Zhao; Limin Liu; Zhiyuan Jiang; Zhenjiang Cao; Jianyun Zhao; Boyang Mao; Wei Yu; Yaqiong Su; R. Vasant Kumar; et al. (Science Bulletin, 2024)

Catalytic diesel soot combustion over FeCo2O4 monolithic catalysts with different morphologies - Zhenhai Fan; Hua Yang; Feiyang Qin; Jieyu Xiao; Hui Xian; Xingchuan Yang; Yi Yu; Guoji Liu; Li Xu; Chunmei Cao (Journal of Environmental Chemical Engineering, 2024)

Increasing biohydrogen production from swine wastewater influenced by anaerobic consortium and nickel ferrite nanoparticles - Jing Ye; Lihua Yu; Juanjuan Cao; Pei Zhao; Qin Zhang; Yanbin Li; Cheng Qian; khadija EI Galai; Mengdie Gao; Xinyu Yang (Fuel, 2024)

Core-shell nanomedicine based on multifunctional tetrahedral DNA nanostructures for synergistic enhancement of tumor chemodynamic/chemo-immunotherapy - Jiansen Li; Chen Cao; Xinlu Zhang; Huan Li; Qin Fan; Shutong Chen; Xu Zhang; Sheng Wang (Chemical Engineering Journal, 2024)

Twisted integration of high-efficiency photothermal/water-transported yarns for boosting solar-powered fabric evaporator - Liming Zhao; Liwen Zhang; Zhengpeng Yang; Tao Zhou; Pei Cao; Li Chen; Yongyi Zhang; Tongtong Qin; Zhenzhong Yong; Kunjie Wu; Qingwen Li (Chemical Engineering Journal, 2024)

The magmatic origin of propylitic alteration of the Zhengguang epithermal Au-Zn deposit, Heilongjiang, China: evidence from mineral compositions and H–O-Sr isotopes - Le Wang; Ming-Jian Cao; Shen Gao; Massimo Chiaradia; Pete Hollings; Ke-Zhang Qin; Xin-Yu Zou; Guo-Xue Song; Xu-Yong Pang; Guang-Ming Li (Mineralium Deposita, 2024)

Soil physicochemical properties and plant functional traits regulate ecosystem multifunctionality of alpine grassland under different livestock grazing assemblies - Bin Feng; Yu-Zhen Liu; Wen-Ting Liu; Wei-Dong Lv; Cai-Cai Sun; Zeng-Zeng Yang; Cai-Di Li; Qin-Yuan Zhou; Fang-Cao Wang; Xiao-Xia Yang; Quan-Min Dong (Agriculture, Ecosystems & Environment, 2024)

Diltiazem HCl suppresses porcine reproductive and respiratory syndrome virus infection in susceptible cells and in swine - Liangliang Li; Jiayu Wang; Li Chen; Qinghai Ren; Muhammad Faheem Akhtar; Wenhua Liu; Changfa Wang; Shengliang Cao; Wenqiang Liu; Qin Zhao; Yubao Li; Tongtong Wang (Veterinary Microbiology, 2024)

Long-term use of etomidate disrupts the intestinal homeostasis and nervous system in mice - Siming Ding; Kan Li; Xing Han; Wenting Lin; Yingjun Qin; Renjuan Cao; Yuan Ren (Toxicology, 2024)

Enhanced biodegradation of microplastic and phthalic acid ester plasticizer: The role of gut microorganisms in black soldier fly larvae - Jiaqing Wang; Cuncheng Liu; Qingcheng Cao; Yun Li; Li Chen; Yuanhang Qin; Tielin Wang; Cunwen Wang (Science of The Total Environment, 2024)

Global prevalence and risk factors associated with Toxoplasma gondii infection in wild birds: A systematic review and meta-analysis - Chao Chen; Si-Yuan Qin; Xing Yang; Xiao-Man Li; Yanan Cai; Cong-Cong Lei; Quan Zhao; Hany M. Elsheikha; Hongwei Cao (Preventive Veterinary Medicine, 2024)

Characteristics of transfer zones under the influence of pre-existing faults and regional stress transformation: Wenchang A subsag, Zhujiang River Mouth Basin, northern South China Sea - Wei Li; Mingyue Cao; Meifang Meng; Caiwei Fan; Hui Li; Jia Li; Wanqiu Wu; Ruiqing Qin; Xingan Li; Yiming Liu (Journal of Oceanology and Limnology, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

A multi-index fusion prediction method for dynamic seismic damage of an arch dam - Lijun Qin; Jianyun Chen; Qiang Xu; Xiangyu Cao; Jing Li (Soil Dynamics and Earthquake Engineering, 2024)

The double-edged effects of La2O3 and CeO2 on the performance of high-rate anaerobic sludge bed reactors and microbial mechanisms - Kai Su; Lin-xiao Li; Zhuo Zeng; Xue Yang; Tao Lei; Han Zhang; Qin Wang; Rong Cao (Process Safety and Environmental Protection, 2024)

Dynamic changes of zinc chemical speciation and zinc-containing peptides release in oysters (Crassostrea hongkongensis) during enzymatic hydrolysis - Ran Du; Wan Li; Jiawei Li; Shan Zeng; Zhongqin Chen; Jialong Gao; Huina Zheng; Haisheng Lin; Guoping Zhu; Xiaoming Qin; Wenhong Cao (Food Bioscience, 2024)

Temporal variation in soil macropore properties and hydraulic conductivity in croplands in the dry-hot valley region of Southwest China - Yi Wang; Yongkang Li; Longxi Cao; Xiaosong Qin; Dongdong Hou (Journal of Soils and Sediments, 2024)

Geochemistry of iron and trace metals in seep carbonates of the middle Okinawa Trough impacted by hydrothermal plumes - Shuang-Shuang Qin; Mao-Xu Zhu; Tie Li; Xilin Zhang; Cuiling Xu; Hong Cao; Wei Geng; Bin Zhai; Ye Chen; Shixing Li; Zhilei Sun (Chemical Geology, 2024)

Fine mapping of a major QTL, qKl-1BL controlling kernel length in common wheat - Ran Qin; Mingsu Cao; Jizi Dong; Linqu Chen; Haoru Guo; Qingjie Guo; Yibiao Cai; Lei Han; Zhenjie Huang; Ninghao Xu; Aoyu Yang; Huiyuan Xu; et al. (Theoretical and Applied Genetics, 2024)

Sinomenine improves resistance to foodborne enteritis and Anti-bacteria mucosal immunity in grass carp - Yuhang Liu; Danying Cao; Nan Wu; Xuyang Zhao; Qingsong Zhu; Lian Su; Fatima Altaf; Qianqian Zhang; Haokun Liu; Yongming Li; Bruno Hamish Unger; Yingyin Cheng; et al. (Aquaculture, 2024)

Black shale LA-ICP-MS Rb-Sr and monazite SIMS U-Pb geochronology from the Cryogenian successions in the northern Yangtze Block - Zhongwu Lan; Kyle Larson; Rong Cao; Qin Ye; Jun Hu; Guoqiang Tang; Jiao Li; Jinnan Tong (Precambrian Research, 2024)

Selection and validation of reference genes for normalization of gene expression in Floccularia luteovirens - Yanqing Ni; Qin Zhang; Wensheng Li; Luping Cao; Rencai Feng; Zhiqiang Zhao; Xu Zhao (Fungal Biology, 2024)

Reference gene selection for quantitative real-time PCR analysis of Hymenopellis radicata under abiotic stress - Luping Cao; Qin Zhang; Renyun Miao; Xu Zhao; Yanqing Ni; Wensheng Li; Rencai Feng; Delong Yang (Fungal Biology, 2024)

Photo-triggered multifunctional gold-based hybrid nanoflowers promote infectious skin regeneration - Jixuan Hong; Jiaqi Zhu; Xiaxin Cao; Boqi Pang; Jiaru Xian; Xueqiong Yin; Qiaoyuan Deng; Maohua Chen; Ziyu Qin; Chaozong Liu; Swastina Nath Varma; Yin Xiao; et al. (Chemical Engineering Journal, 2024)

Comparison of phosphorus migration and transformation characteristics in sediments of lakes within the Yangtze River basin and reservoirs on the Wujiang River - Hui Li; Yingying Cai; Chunlei Song; Zhong Cao; Ji Li; Zhenhua Qin; Shunxi Zhang; Jianfen Li; Xiuyun Cao; Yiyong Zhou (Journal of Soils and Sediments, 2024)

Caffeine intake enhances peak oxygen uptake and performance during high-intensity cycling exercise in moderate hypoxia - Tze-Huan Lei; Qiyang Qin; Olivier Girard; Toby Mündel; Ran Wang; Li Guo; Yinhang Cao (European Journal of Applied Physiology, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Anisotropic Rayleigh wave tomography revealed lithospheric modification and tectonic deformation mechanisms in Hubei Province, central China - Tengfei Wu; Zi-Jun Cao; Mengkui Li; Shuangxi Zhang; Liping Qin (Tectonophysics, 2024)

Particle size-dependent and route-specific exposure to liquid crystal monomers in indoor air: Implications for human health risk estimations - Huiju Lin; Xinxing Li; Xian Qin; Yaru Cao; Yuefei Ruan; Michael K.H. Leung; Kenneth M.Y. Leung; Paul K.S. Lam; Yuhe He (Science of The Total Environment, 2024)

Assessment of heavy metals concentrations in five marine organisms from Lianyungang in China and the corresponding health risk - Ya-Qin Zhang; Chun-Hui Gong; Xiang-Hua Qi; Wen-Jun Wang; Peng-Tao Cao; Qiang Li; Peng Wang; Yi Yang (Regional Studies in Marine Science, 2024)

Active/passive protection and anti-UV waterborne epoxy coatings based on low defect functionalized PDA-GO-CeO2 material for excellent corrosion control - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Hao-Jie Yan; Hui-Song Hu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2024)

Effects of Thirty Days Isolation on Attention Networks: A Behavioral and Event-related Potential Study - Jingda Feng; Bin Wu; Ziqing Cao; Hailong Chen; Tianjun Lan; Haibo Qin; Yusheng Shi; Weifen Huang; Yinghui Li (Neuroscience Bulletin, 2024)

CD4 is an important host factor for Japanese encephalitis virus entry and replication in PK-15 cells - Qi Wang; Shuqing Yang; Ke Yang; Xinran Li; Yu Dai; Yi Zheng; Sanjie Cao; Qigui Yan; Xiaobo Huang; Yiping Wen; Qin Zhao; Senyan Du; et al. (Veterinary Microbiology, 2023)

Salviamilthone A-O, diterpenoid quinones from Salvia miltiorrhiza - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Qin-Qin Zhang; Yan-Ling Liu; Chen He; Xu Chen; Xi-Ling Fan; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

Influence of key geological factors on fluid production behaviors in marine natural gas hydrate reservoirs: A case study - Yuhang Gu; Tianle Liu; Jiaxin Sun; Fanfan Qin; Xinxin Cao; Shunbo Qin; Yanlong Li; Ling Zhang; Fulong Ning; Guosheng Jiang (Ocean Engineering, 2023)

A 4.43-Kb deletion of chromosomal segment containing an ovate family protein confers long capsule in sesame (Sesamum indicum L.) - Cuiying Wang; Jiaojiao Niu; Libin Wei; Chun Li; Guiting Li; Qiuzhen Tian; Ming Ju; Qin Ma; Hengchun Cao; Yinghui Duan; Hui Guo; Haiyang Zhang; et al. (Theoretical and Applied Genetics, 2023)

Effects of urbanization on fungal communities and their functions in the sediment of the Haihe River - Guangtao Li; Lihua Cao; Xiuli Li; Hongyan Zhao; Mingyue Chang; Dan Lu; Lingyan Zhang; Mingming Li; Tingting Qin; Huihu Jin; Xin Li; Jiangong Wang; et al. (Journal of Soils and Sediments, 2023)

Quantitative calculation of gases generation during low-temperature oxidation of coal - Jinhu Li; Qin Cao; Wei Lu; Jingjuan Geng; Jinliang Li; Hui Zhuo (Environmental Science and Pollution Research, 2023)

Nitrogen removal performances and metabolic mechanisms of denitrification systems using different volatile fatty acids as external carbon sources - Xin Li; Xiangzhen Li; Chaonan Li; Na Li; Ping Zou; Xiaolong Gao; Qin Cao (Chemical Engineering Journal, 2023)

Optimization of SbBix nanoparticles embedded in ultra-thin carbon networks for enhanced sodium/potassium storage - Qingxin Lin; Jian Qin; Yanyan Cao; Xiaokang Li; Yan Hong; Meichen Jin; Jinjuan Dong; Wei Xiao; Wenbin Li; Jingjing Wang; Xifei Li (Chemical Engineering Journal, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

The Epidemiology of Tinea Capitis in Guangxi Province, China - Dongyan Zheng; Tianwei Liang; Weixuan Wu; Najwa Al-Odaini; Kaisu Pan; Lan Huang; Guomei Huang; Lulu Tang; Xinlei Li; Shao He; Huahui Jian; Nibo Wei; et al. (Mycopathologia, 2023)

Effects of insulin-like growth factor 1, leukemia inhibitory factor, and basic fibroblast growth factor on goat oocyte maturation and early embryonic development in vitro - Zhao Gao-Ping; Shi Pei-Xin; Chang Qing; Wang Zi-Xin; Li Yun-Xia; Zhao Li-Xia; Sun Wei; Wu Meng; Bao Si-Qin; Cao Gui-Fang; Li Xi-He (Small Ruminant Research, 2023)

Genetic diversity, antibiotic resistance, and virulence characteristics of Staphylococcus aureus from raw milk over 10 years in Shanghai - Jiewen Huang; Wengang Zhang; Bingqing Sun; Qin Jiang; Ying Cao; Jun Shang; Yu Zhang; Xin Gu; Chao Lv; Chaoyi Guo; Min Li; Hui Li; et al. (International Journal of Food Microbiology, 2023)

Kinetically accelerated oxygen evolution reaction in metallic (oxy)hydroxides enabled by Cr-dopant and heterostructure - Feng Cao; Mengyang Li; Yixuan Hu; Xinge Wu; Xin Li; Xiangying Meng; Peng Zhang; Song Li; Gaowu Qin (Chemical Engineering Journal, 2023)

Continuous Co-incorporation of Chinese Milk Vetch and Rice Straw with Reduced Chemical Fertilizer Maintains Rice Yield as a Consequence of Increased Carbon and Nitrogen Storage in Soil Aggregates - Rongyan Bu; Wenlong Cheng; Shang Han; Run Hu; Hui Wang; Shan Tang; Min Li; Qin Zhu; Ji Wu; Weidong Cao (Journal of Soil Science and Plant Nutrition, 2023)

Pyrroloquinoline quinone promotes growth and intestinal health and alleviates tris(1,3-dichloro-2-propyl) phosphate-induced hepatic oxidative stress in zebrafish - Chao-Qun Li; Yong-Jun Cao; Long-Fei Cui; Chun-Yang Zhang; Bei-Li Zhang; Qin-Yuan Ma (Aquaculture, 2023)

A thermal radiation directionality correction method for the surface upward longwave radiation of geostationary satellite based on a time-evolving kernel-driven model - Boxiong Qin; Biao Cao; Jean-Louis Roujean; Jean-Philippe Gastellu-Etchegorry; Sofia L. Ermida; Zunjian Bian; Yongming Du; Tian Hu; Hua Li; Qing Xiao; Shuisen Chen; Qinhuo Liu (Remote Sensing of Environment, 2023)

Arsenate removal from water by Ti electrocoagulation: Main influencing factors, response surface optimization, and potential mechanisms - Jie Li; Yumin Cao; Jianbo Lu; Changcai Qin; Wei Zhang; Xintong Zhang; Xuesong Yi; Wenzheng Yu (Journal of Water Process Engineering, 2023)

Emerging roles of air pollution and meteorological factors in autoimmune eye diseases - Fan Cao; Zhuo-Ran Liu; Qin-Yu Ni; Chen-Kai Zha; Shu-Jie Zhang; Jia-Min Lu; Yue-Yang Xu; Li-Ming Tao; Zheng-Xuan Jiang; Hai-Feng Pan (Environmental Research, 2023)

An ultrafast water absorption composite cryogel containing Iron-doped bioactive glass with rapid hemostatic ability for non-compressible and coagulopathic bleeding - Maocai Li; Qiyuan Dai; Shuangli Zhu; Qi Feng; Zhihao Qin; Huichang Gao; Xiaodong Cao (Chemical Engineering Journal, 2023)

Micro-mechanism insights into the adsorption of anionic dyes using quaternary ammonium-functionalised chitosan aerogels - Nan Du; Li-Yuan Huang; Yan-Shu Xiong; Run Tian; Jiang-Yu Yin; Dan-Yu Cao; Dong-Bin Hu; Hai-Qin Lu; Wen Li; Kai Li (Carbohydrate Polymers, 2023)

Dansyl-labelled cellulose as dual-functional adsorbents for elimination and detection of mercury in aqueous solution via aggregation-induced emission - Ming Li; Siqi Zhang; Panpan Zhang; Kexin Qin; Qian Chen; Qianyong Cao; Yuling Zhang; Jinghong Zhang; Chungang Yuan; Huining Xiao (Journal of Environmental Management, 2023)

One global disseminated 193 kb high-risk hybrid plasmid harboring tet(X4), mcr or blaNDM threatening public health - Min Li; Haoran Zhang; Wengang Zhang; Ying Cao; Bingqing Sun; Qin Jiang; Yu Zhang; Haodong Liu; WenNan Guo; Cheng Chang; Nan Zhou; Chao Lv; et al. (Science of The Total Environment, 2023)

Holocene warming trend based on peat brGDGTs records from southeastern humid to northwestern arid China - Shikai Wei; Zhiguo Rao; Jiantao Cao; Guodong Jia; Yunxia Li; Haichun Guo; Zixian Feng; Kaiyue Guang; Qianqian Qin; Yiping Tian; Jiayan Li; Siqi Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

A novel cerium organic network modified graphene oxide prepared multifunctional waterborne epoxy-based coating with excellent mechanical and passive/active anti-corrosion properties - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Pan Liu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Upgrading the accumulation of ginsenoside Rd in Panax notoginseng by a novel glycosidase-producing endophytic fungus G11-7 - Lili Niu; Xiangyu Qin; Litao Wang; Na Guo; Hongyan Cao; Hanghang Li; Chunjian Zhao; Huimei Wang; Yujie Fu (Folia Microbiologica, 2023)

Correction: Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Chlorogenic acid, rutin, and quercetin from Lysimachia christinae alleviate triptolide-induced multi-organ injury in vivo by modulating immunity and AKT/mTOR signal pathway to inhibit ferroptosis and apoptosis - Xiaohui Wu; Junming Wang; Bingyin Li; Mingzhu Gong; Can Cao; Lingling Song; Lingyu Qin; Yanmei Wang; Yueyue Zhang; Yamin Li (Toxicology and Applied Pharmacology, 2023)

Effects of cold atmospheric plasma on endogenous enzyme activity and muscle protein oxidation in Trachinotus ovatus - Huiyuan Situ; Yumei Li; Jialong Gao; Chaohua Zhang; Xiaoming Qin; Wenhong Cao; Haisheng Lin; Zhongqin Chen (Food Chemistry, 2023)

A Strecker-like reaction triggering fluorescent sensing platform for enzyme-free and visual quantitative monitoring of carbamates - Lingling Qin; Jie Cao; Dan Lin; Shihao Xu; Yucheng Li; Changlong Jiang (Chemical Engineering Journal, 2023)

Dual-quenching mechanisms in electrochemiluminescence immunoassay based on zinc-based MOFs of ruthenium hybrid for D-dimer detection - Guanhui Zhao; Yu Du; Nuo Zhang; Chenchen Li; Hongmin Ma; Dan Wu; Wei Cao; Yaoguang Wang; Qin Wei (Analytica Chimica Acta, 2023)

BPA induces placental trophoblast proliferation inhibition and fetal growth restriction by inhibiting the expression of SRB1 - Yuming Cao; Sihan Chen; Jing Lu; Ming Zhang; Lei Shi; Juling Qin; Jing Lv; Danyang Li; Ling Ma; Yuanzhen Zhang (Environmental Science and Pollution Research, 2023)

VOC emission profiles from typical solid fuel combustion in Fenhe River Basin: Field measurements and environmental implication - Qin Peng; Lizhen Li; Jian Sun; Kun He; Bin Zhang; Haijiang Zou; Hongmei Xu; Junji Cao; Zhenxing Shen (Environmental Pollution, 2023)

Power to biogas upgrading: Effects of different H2/CO2 ratios on products and microbial communities in anaerobic fermentation system - Zhijie Xie; Siyuan Huang; Yuqin Wan; Fang Deng; Qin Cao; Xiaofeng Liu; Dong Li (Science of The Total Environment, 2023)

Comparative transcriptome analysis of non-germinated and germinated spores of Enterocytozoon hepatopenaei (EHP) in vitro - Yabin Dou; Leiting Zhang; Hui Shen; Sheng Zhang; Xiaohui Cao; Yi Qiao; Ge Jiang; Jie Cheng; Xihe Wan; Xianping Fan; Hui Li; Libao Wang; et al. (Journal of Invertebrate Pathology, 2023)

Low C/N promotes stable partial nitrification by enhancing the cooperation of functional microorganisms in treating high-strength ammonium landfill leachate - Qin Cao; Yichao Chen; Xin Li; Chaonan Li; Xiangzhen Li (Journal of Environmental Management, 2023)

SmJAZ4 interacts with SmMYB111 or SmMYC2 to inhibit the synthesis of phenolic acids in Salvia miltiorrhiza - Rao Yang; Shasha Li; Shuai Dong; Long Wang; Huiting Qin; Hongbin Zhan; Donghao Wang; Xiaoyan Cao; Hongxing Xu (Plant Science, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Oxygen vacancy mediated α-MoO3 bactericidal nanocatalyst in the dark: Surface structure dependent superoxide generation and antibacterial mechanisms - Qin Gao; Zhenyu Wang; Yongfang Rao; Yulei Zhao; Junji Cao; Kin-Fai Ho; Yue Zhai; Mingyu Xiong; Juntang Li; Yu Huang (Journal of Hazardous Materials, 2023)

Magnetic metal–organic frameworks as adsorbents for the detection of azo pigments in food matrices - Lei Cheng; Rong Huang; Qiang Cao; Na Liu; Peiyi Li; Mengmeng Sun; Haiyang Qin; Lidong Wu (Food Chemistry, 2023)

Rapamycin ameliorates brain damage and maintains mitochondrial dynamic balance in diabetic rats subjected to middle cerebral artery occlusion - Changchun Hei; Yujia Zhou; Chenyang Zhang; Furong Gao; Meiling Cao; Shilin Yuan; Yixin Qin; P. Andy Li; Xiao Yang (Metabolic Brain Disease, 2023)

Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Efficient removal of bisphenol A by a novel biochar-based Fe/C granule via persulfate activation: Performance, mechanism, and toxicity assessment - Xiang Li; Yang Qin; Huajing Song; Wei Zou; Zhiguo Cao; Linjie Ding; Yuwei Pan; Minghua Zhou (Process Safety and Environmental Protection, 2023)

Puerol and pueroside derivatives from Pueraria lobata and their anti-inflammatory activity - Ying-Jie Sun; Shi-Jie Cao; Feng-Ni Liang; Jin-Yan Li; Xiang-Yu Zhang; Wei Li; Li-Qin Ding; Feng Qiu (Phytochemistry, 2023)

A novel method for preparing tungsten and molybdenum peroxy complex solution and its application to tungsten - molybdenum separation - Xinbing Xia; Guiqing Zhang; Wenjuan Guan; Qin Zhou; Li Zeng; Shengxi Wu; Qinggang Li; Zuoying Cao; Kaiyuan Fang; Chonglong Shi (Hydrometallurgy, 2023)

High-efficient and recoverable Mo72V30@Fe3O4/C catalyst for oxidation of hydroxyfurfural - Mengdi Gong; Xin-Yu Wang; Mu-Qin Li; Wen-Xia Mu; Yun-Dong Cao; Hong Liu; Yu-Guang Lv; Xin-Hua Qi; Guang-Gang Gao (Fuel, 2023)

The microbial and functional reconstruction of instable syntrophic propionate-oxidizing methanogenesis by system recovering and injection modes changing - Dong Li; Xianghui Meng; Yong Sun; Xin Li; Xiaofeng Liu; Zhijie Xie; Qin Cao (Chemical Engineering Journal, 2023)

Knockdown of lncRNA-ASLNC12002 alleviates epithelial–mesenchymal transition of type II alveolar epithelial cells in sepsis-induced acute respiratory distress syndrome - Kaixuan Feng; Weifeng Huang; Jiawei Shang; Feng Ping; Qin Tan; Wei Wang; Yingchuan Li; Yongmei Cao (Human Cell, 2022)
Patients with sepsis-induced acute respiratory distress syndrome (ARDS) have higher mortality and poor prognosis than pneumonia-induced ARDS. Pulmonary fibrosis is an irreversible accumulation of connective tissue in the interstitium of the lung and closely associated with the epithelial–mesenchymal transition (EMT) of type II alveolar epithelial cells (AECIIs). Therefore, it is undoubtedly worth studying whether the EMT of AECIIs in sepsis-induced ARDS patients is different from that in patients with pneumonia-induced ARDS in the regulatory mechanism. Here, we will report for the first time that an lncRNA-ASLNC12002 is highly expressed in AECIIs of patients with sepsis-induced pneumonia and promotes EMT in AECIIs. The research results showed that the expression of ASLNC12002 in AECIIs derived from patients with sepsis-induced ARDS is significantly higher than that in normal people and pneumonia-induced ARDS patients. Mechanism research showed that ASLNC12002 can cause the inactivation of the anti-EMT pathway NR2F2/miR128-3p/Snail1 by acting as the sponge of miR128-3p. Functional experiments showed that targeted silencing of ASLNC12002 could effectively inhibit EMT progression in AECIIs of patients with sepsis-induced pneumonia by restoring NR2F2/miR128-3p/Snail1 pathway. In a word, our study shows for the first time that the inactivation of NR2F2/miR128-3p/Snail1 pathway caused by the enhanced expression of ASLNC12002 is the direct reason why AECIIs in sepsis-induced ARDS patients are prone to get EMT progress. ASLNC12002 has the potential to become a biological target for the prevention and treatment of pulmonary fibrosis in patients with sepsis-induced ARDS. At the same time, the expectation that ASLNC12002 and its related products may be used as clinical markers for the evaluation of early pulmonary fibrosis in ARDS patients should not be ignored.

PDGFD switches on stem cell endothelial commitment - Weisi Lu; Peipei Xu; Boxiong Deng; Jianing Zhang; Ying Zhan; Xianchai Lin; Xiangzhong Xu; Zhaoxia Xia; Xiaoxi Yang; Xiaoling Zeng; Lijuan Huang; Bingbing Xie; et al. (Angiogenesis, 2022)
The critical factors regulating stem cell endothelial commitment and renewal remain not well understood. Here, using loss- and gain-of-function assays together with bioinformatic analysis and multiple model systems, we show that PDGFD is an essential factor that switches on endothelial commitment of embryonic stem cells (ESCs). PDGFD genetic deletion or knockdown inhibits ESC differentiation into EC lineage and increases ESC self-renewal, and PDGFD overexpression activates ESC differentiation towards ECs. RNA sequencing reveals a critical requirement of PDGFD for the expression of vascular-differentiation related genes in ESCs. Importantly, PDGFD genetic deletion or knockdown increases ESC self-renewal and decreases blood vessel densities in both embryonic and neonatal mice and in teratomas. Mechanistically, we reveal that PDGFD fulfills this function via the MAPK/ERK pathway. Our findings provide new insight of PDGFD as a novel regulator of ESC fate determination, and suggest therapeutic implications of modulating PDGFD activity in stem cell therapy.

Numerical Simulation of Fully Coupled Flow-Field and Operational Limitation Envelopes of Helicopter-Ship Combinations - Yihua Cao; Yihao Qin; Wenyuan Tan; Guozhi Li (Journal of Marine Science and Engineering, 2022)
Landing a helicopter to the ship flight deck is most demanding even for the most experienced pilots and modeling and simulation of the ship-helicopter dynamic interface is a substantially challenging technical problem. In this paper, a coupling numerical method was developed to simulate the fully coupled ship-helicopter flow-field under complete wind-over-deck conditions. The steady actuator disk model based on the momentum source approach and the resolved blade method based on the moving overset mesh method were employed to model the rotor. Two different ship-helicopter combinations were studied. The helicopter flight mechanics model was established and then the influences of coupled airwake on the helicopter were analyzed. Finally, based on the derived rejection criterion of safe landing and the developed numerical method, the flight envelopes for these two ship-helicopter combinations were predicted. The steady actuator disk model was found to be effective in the study of helicopter operations in the shipboard environment. The calculated flight envelopes indicate that an appropriate wind direction angle is beneficial to increasing the allowable maximum wind speed and the operating boundary is affected by the rotation direction of the main rotor.

MYOCD is Required for Cardiomyocyte-like Cells Induction from Human Urine Cells and Fibroblasts Through Remodeling Chromatin - Xiangyu Zhang; Lijun Chen; Xingnan Huang; Huan Chen; Baomei Cai; Yue Qin; Yating Chen; Sihua Ou; Xiaoxi Li; Zichao Wu; Ziyu Feng; Mengying Zeng; et al. (Stem Cell Reviews and Reports, 2022)

Expression patterns and correlation analyses of muscle-specific genes in the process of sheep myoblast differentiation - Hejie Wang; Minmin Dou; Jun Li; Peng Cao; Junling Li; Tianyan Guo; Dipeng Zhao; Ajab Khan; Yingliang Li; Baojun Li; Jian Qin; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2022)

Motor imagery evokes strengthened activation in sensorimotor areas and its effective connectivity related to cognitive regions in patients with complete spinal cord injury - Ling Wang; Xuejing Li; Weimin Zheng; Xin Chen; Qian Chen; Yongsheng Hu; Lei Cao; Jian Ren; Wen Qin; Jie Lu; Nan Chen (Brain Imaging and Behavior, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Relationship of night sleep duration with health lifestyle, depressive symptoms, internet addiction in Chinese High school Students - Yueyang Hu; Tingting Gao; Ruilin Cao; Hui Ren; Zeying Qin; Chuanen Li; Leilei Liang; Cuicui Meng; Xinmeng Guo; Jianping Lv; Songli Mei (Sleep and Biological Rhythms, 2022)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

Whole-Transcriptome Analysis of Serum L1CAM-Captured Extracellular Vesicles Reveals Neural and Glycosylation Changes in Autism Spectrum Disorder - Yannan Qin; Li Cao; Jinyuan Zhang; Haiqing Zhang; Shuang Cai; Bo Guo; Fei Wu; Lingyu Zhao; Wen Li; Lei Ni; Liying Liu; Xiaofei Wang; et al. (Journal of Molecular Neuroscience, 2022)

Application of pretensioned grouting support in repairing surrounding rock damaged by dynamic load - Zhongcheng Qin; Yongle Liu; Jinxiao Liu; Bin Cao; Feng Zhang; Wenxin Li (Arabian Journal of Geosciences, 2022)

The Predominance of Nongrowing Season Emissions to the Annual Methane Budget of a Semiarid Alpine Meadow on the Northeastern Qinghai-Tibetan Plateau - Hongqin Li; Jingbin Zhu; Fawei Zhang; Gang Qin; Yongsheng Yang; Yikang Li; Junbang Wang; Guangmin Cao; Yingnian Li; Huakun Zhou; Mingyuan Du (Ecosystems, 2022)

Diversity and spatiotemporal dynamics of fungal communities in the rhizosphere soil of Lycium barbarum L.: a new insight into the mechanism of geoherb formation - Yuekun Li; Kaili Chen; Siyang Liu; Xiaojie Liang; Yajun Wang; Xuan Zhou; Yue Yin; Youlong Cao; Wei An; Ken Qin; Yanfei Sun (Archives of Microbiology, 2022)
Lycium barbarum L. is a well-known traditional geoherb in Ningxia, China. The fruits of L. barbarum contain several dietary constituents, and thus, they exert many beneficial effects on human health. However, a few studies have been conducted on the geoherb L. barbarum and its rhizosphere soil fungal community. In this study, we determined the physicochemical properties and fungal community structure of rhizosphere soil of L. barbarum from three regions of China, namely Ningxia (NX), Qinghai (QH), and Xinjiang (XJ), during three development stages of L. barbarum . Soil pH varied between 7.56 and 8.60 across the three regions, indicating that alkaline soil is conducive to the growth of L. barbarum . The majority of soil properties in NX, an authentic geoherb-producing area, were substantially inferior to those in XJ and QH during all three developmental stages. Total sugar, polysaccharide (LBP), and flavonoid contents were the highest in wolfberry fruits from NX. High-throughput sequencing showed that the abundance of the soil fungal population in NX was higher than that in QH and XJ during the flowering and fruiting stage and summer dormant stage. Moreover, the soil fungal diversity increased with the development of wolfberry. Ascomycota and Mortierellomycota were the predominant phyla in the rhizosphere fungal communities in all samples. Redundancy analysis showed a significant correlation of the soil-available phosphorus and LBP of wolfberry fruits with the fungal community composition. The characteristics of rhizosphere fungal communities determined in the present study provide insights into the mechanism of geoherb formation in NX wolfberry.

Dietary pectin caused great changes in bile acid profiles of Pelteobagrus fulvidraco - Xiamin Cao; Shengjie Ren; Chunfang Cai; Qin Ni; Xinyue Li; Yunhe Meng; Zijing Meng; Ye Shi; Huangen Chen; Rong Jiang; Ping Wu; Yuantu Ye (Fish Physiology and Biochemistry, 2021)

Cytochalasins from endophytic Diaporthe sp. GDG-118 - Xishan Huang; Dexiong Zhou; Yan Liang; Xiaobo Liu; Fei Cao; Yuyue Qin; Tuxiang Mo; Zhaolong Xu; Jun Li; Ruiyun Yang (Natural Product Research, 2021)

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

Spatio-temporal evolution and future scenario prediction of karst rocky desertification based on CA–Markov model - Fei Chen; Shijie Wang; Xiaoyong Bai; Fang Liu; Yichao Tian; Guangjie Luo; Qin Li; Jingfeng Wang; Luhua Wu; Yue Cao; Huiwen Li; Yuanhong Deng; et al. (Arabian Journal of Geosciences, 2021)

Characteristics of Modern Geostress and Removability of No. 15 Coal Reservoir, Yangquan Mining Area, China - Tengfei Cao; Zhaobiao Yang; Yong Qin; Zhiming Yan; Zhaoying Chen; Chao Li (Natural Resources Research, 2021)

Titanite in situ SIMS U–Pb geochronology, elemental and Nd isotopic signatures record mineralization and fluid characteristics at the Pusangguo skarn deposit, Tibet - MingJian Cao; KeZhang Qin; Noreen J. Evans; GuangMing Li; XiaoXiao Ling; Brent I. A. McInnes; JunXing Zhao (Mineralium Deposita, 2021)

Occurrence, spatial distribution, source, and ecological risk assessment of organochlorine pesticides in Dongting Lake, China - Fengmei Cao; Zhaozhao Li; Qi He; Shaoyong Lu; Pan Qin; Linlin Li (Environmental Science and Pollution Research, 2021)

The formation and evolution of parent and oxygenated polycyclic aromatic hydrocarbons during a severe winter haze–fog event over Xi’an, China - Yali Lei; Zhenxing Shen; Kun He; Lijuan Li; Yiming Qin; Yaling Zeng; Jianjun Li; Hongmei Xu; Yongjing Ma; Tian Zhang; Liu Yang; Ningning Zhang; et al. (Environmental Science and Pollution Research, 2021)

Influence of plant coverage and environmental variables on pollen productivities: evidence from northern China - Kaixiu Zhang; Wen Qin; Fang Tian; Xianyong Cao; Yuecong Li; Jule Xiao; Wei Ding; Ulrike Herzschuh; Qinghai Xu (Frontiers of Earth Science, 2020)

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Simulation of drainage hole arrays and seepage control analysis of the Qingyuan Pumped Storage Power Station in China: a case study - Zengguang Xu; Cheng Cao; Kanghong Li; Junrui Chai; Wei Xiong; Junyu Zhao; Ronggao Qin (Bulletin of Engineering Geology and the Environment, 2019)

Effects of dietary protein level on growth performance, digestive enzyme activity, and gene expressions of the TOR signaling pathway in fingerling Pelteobagrus fulvidraco - Qin Qin; Xiu-Fei Cao; Yong-jun Dai; Li-Na Wang; Ding-Dong Zhang; Guang-Zhen Jiang; Wen-Bin Liu (Fish Physiology and Biochemistry, 2019)

Fluorine-modified sialyl-Tn-CRM197 vaccine elicits a robust immune response - Chengcheng Song; Xiu-Jing Zheng; Haili Guo; Yafei Cao; Fan Zhang; Qin Li; Xin-Shan Ye; Yifa Zhou (Glycoconjugate Journal, 2019)

MicroRNA-377-3p inhibits growth and invasion through sponging JAG1 in ovarian cancer - Liulin Tang; Bin Yang; Xiaolan Cao; Qin Li; Li Jiang; Dan Wang (Genes & Genomics, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Review on the determination and distribution patterns of a widespread contaminant artificial sweetener in the environment - Jingyang Luo; Lijuan Wu; Qin Zhang; Yang Wu; Fang Fang; Qian Feng; Chao Li; Zhaoxia Xue; Jiashun Cao (Environmental Science and Pollution Research, 2019)

Role of Maize Root Exudates in Promotion of Colonization of Bacillus velezensis Strain S3-1 in Rhizosphere Soil and Root Tissue - Yeqing Jin; Hangfei Zhu; Si Luo; Wenwu Yang; Li Zhang; Shanshan Li; Qing Jin; Qin Cao; Shurong Sun; Ming Xiao (Current Microbiology, 2019)

Eremophilane sesquiterpenes from the endophytic fungus Xylaria sp. GDG-102 - Yan Liang; Weifeng Xu; Chengmei Liu; Dexiong Zhou; Xiaobo Liu; Yuyue Qin; Fei Cao; Jun Li; Ruiyun Yang; Jiangke Qin (Natural Product Research, 2019)

Ichthyoplankton recruitment from mainstream of the Changjiang River into the Dongting Lake, the second largest freshwater lake in China - Qin Ma; Mingzheng Li; Xiangchao Qin; Huanzhang Liu; Wenxuan Cao (Journal of Oceanology and Limnology, 2019)

Correction to: Rapid Genomic and Genetic Changes in the First Generation of Autotetraploid Lineages Derived from Distant Hybridization of Carassius auratus Red Var. (♀) × Megalobrama amblycephala (♂) - Qinbo Qin; Liu Cao; Yude Wang; Li Ren; Qiwen Liu; Yuwei Zhou; Chongqing Wang; Huan Qin; Chun Zhao; Shaojun Liu (Marine Biotechnology, 2019)

Rapid Genomic and Genetic Changes in the First Generation of Autotetraploid Lineages Derived from Distant Hybridization of Carassius auratus Red Var. (♀) × Megalobrama amblycephala (♂) - Qinbo Qin; Liu Cao; Yude Wang; Li Ren; Qiwen Liu; Yuwei Zhou; Chongqing Wang; Huan Qin; Chun Zhao; Shaojun Liu (Marine Biotechnology, 2019)

A comparison of dynamic distributions of intestinal microbiota between Large White and Chinese Shanxi Black pigs - Pengfei Gao; Yadan Liu; Baoyu Le; Benyuan Qin; Min Liu; Yuanyuan Zhao; Xiaohong Guo; Guoqing Cao; Jianfeng Liu; Bugao Li; Zhibian Duan (Archives of Microbiology, 2019)

Development of a sensitive and reliable reverse transcription droplet digital PCR assay for the detection of citrus yellow vein clearing virus - Yingjie Liu; Yingli Wang; Qin Wang; Yanhui Zhang; Wanxia Shen; Ruhui Li; Mengji Cao; Lei Chen; Xue Li; Changyong Zhou; Yan Zhou (Archives of Virology, 2019)

Recovery of unstable digestion of vegetable waste by adding trace elements using the bicarbonate alkalinity to total alkalinity ratio as an early warning indicator - Dong Li; Juan Sun; Qin Cao; Yichao Chen; Xiaofeng Liu; Yi Ran (Biodegradation, 2019)

New automated method for extracting river information using optimized spectral threshold water index - Chaojun Li; Shijie Wang; Xiaoyong Bai; Qiu Tan; Yujie Yang; Qin Li; Luhua Wu; Jianyong Xiao; Qinghuan Qian; Fei Chen; Huiwen Li; Yue Cao; et al. (Arabian Journal of Geosciences, 2019)

Detection and quantification of Aeromonas schubertii in Channa maculata by TaqMan MGB probe fluorescence real‐time quantitative PCR - Chun Liu; Yanming M. Guo; Jizhen Z. Cao; De‐Feng Zhang; Ou‐Qin Chang; Kaibin Li; Fang Wang; Cun‐Bin Shi; Lan Jiang; Qing Wang; Li Lin (Journal of Fish Diseases, 2019)
Aeromonas schubertii is a major epidemiological agent that threatens cultured snakeheads ( Channidae ) and has caused great economic losses in fish‐farming industries in China in recent years. In present study, a specific TaqMan minor groove binder ( MGB ) probe fluorescence real‐time quantitative PCR ( qPCR ) assay was developed to rapidly detect and quantify A. schubertii . A pair of qPCR primers and a TaqMan MGB probe were selected from the rpoD gene, which were shown to be specific for A. schubertii . A high correlation coefficient ( R 2 = 0.9998) in a standard curve with a 103% efficiency was obtained. Moreover, the qPCR method's detection limit was as low as 18 copies/μl, which was 100 times more sensitive than that of conventional PCR . The detection results for the A. schubertii in pond water and fish tissue were consistent with those of the viable counts. Bacterial load changes detected by qPCR in different tissues of snakeheads infected with A. schubertii showed that the gills and intestines may be the entry for A. schubertii , and the spleen and kidney are major sites for A. schubertii replication. The established method in present study should be a useful tool for the early surveillance and quantitation of A. schubertii .

Optimization of Hydrolysis Conditions for the Isolation of Angiotensin-I Converting Enzyme (ACE) Inhibitory Peptides from Rhopilema hispidum - Zhenliang Sun; Huanlong Qin; Duo Cao; Xuebing Yan; Hao Li; Linsheng Huang; Xiao Qu; Cheng Kong; Man Wang (Journal of Ocean University of China, 2018)

High Selenium Yeast mitigates aluminum-induced cerebral inflammation by increasing oxidative stress and blocking NO production - Changyu Cao; Xiaowen Li; Lei Qin; Junchong Luo; Mengdan Zhang; Zijian Ou; Kai Wang (BioMetals, 2018)

Using Illumina-Based Sequence Analysis to Guide Probiotic Candidate Selection and Isolation - Wenfeng Wang; Yi Li; Wangsen Qin; Changyi Sun; Hongming Tan; Lixiang Cao (Probiotics and Antimicrobial Proteins, 2018)

Supercritical carbon dioxide extract of Cinnamomum cassia bark: toxicity and repellency against two stored-product beetle species - Yang Wang; Pei-Pei Dai; Shan-Shan Guo; Ju-Qin Cao; Xue Pang; Zhu-Feng Geng; Yu-Li Sang; Shu-Shan Du (Environmental Science and Pollution Research, 2018)

Full genome sequence of the first bluetongue virus serotype 21 (BTV-21) isolated from China: evidence for genetic reassortment between BTV-21 and bluetongue virus serotype 16 (BTV-16) - Shaomin Qin; Heng Yang; Yixuan Zhang; Zhanhong Li; Jun Lin; Lin Gao; Defang Liao; Yingying Cao; Pengfei Ren; Huachun Li; Jianmin Wu (Archives of Virology, 2018)

The key gluconeogenic gene PCK1 is crucial for virulence of Botrytis cinerea via initiating its conidial germination and host penetration - Jian‐Kang Liu; Hao‐Wu Chang; Yue Liu; Yu (Haity) Qin; Yu‐Han Ding; Lan Wang; Yue Zhao; Ming‐Zhe Zhang; Sheng‐Nan Cao; Le‐Tao Li; Wei Liu; Gui‐Hua Li; et al. (Environmental Microbiology, 2018)
Summary The process of initiation of host invasion and survival of some foliar phytopathogenic fungi in the absence of external nutrients on host leaf surfaces remains obscure. Here, we demonstrate that gluconeogenesis plays an important role in the process and nutrient‐starvation adaptation before the pathogen host invasion. Deletion of phosphoenolpyruvate c arboxy k inase gene BcPCK1 in gluconeogenesis in Botrytis cinerea , the causative agent of grey mould, resulted in the failure of the Δ Bcpck1 mutant conidia to germinate on hard and hydrophobic surface and penetrate host cells in the absence of glucose, reduction in conidiation and slow conidium germination in a nutrient‐rich medium. The wild‐type and Δ Bcpck1 conidia germinate similarly in the presence of glucose (higher concentration) as the sole carbon source. Conidial glucose‐content should reach a threshold level to initiate germination and host penetration. Infection structure formation by the mutants displayed a glucose‐dependent fashion, which corresponded to the mutant virulence reduction. Exogenous glucose or complementation of BcPCK1 completely rescued all the developmental and virulence defects of the mutants. Our findings demonstrate that BcPCK1 plays a crucial role in B. cinerea pathogenic growth and virulence, and provide new insights into gluconeogenesis mediating pathogenesis of plant fungal pathogens via initiation of conidial germination and host penetration.

The pre‐rRNA processing factor Nop53 regulates fungal development and pathogenesis via mediating production of reactive oxygen species - Sheng‐Nan Cao; Ye Yuan; Yu (Haity) Qin; Ming‐Zhe Zhang; Paul de Figueiredo; Gui‐Hua Li; Qing‐Ming Qin (Environmental Microbiology, 2018)
Summary Botrytis cinerea is a necrotrophic plant fungal pathogen that annually causes enormous economic losses worldwide. The ribosome is an organelle for cellular protein biosynthesis. However, little is known about how the ribosome operates as a machine to mediate microbial pathogenesis. Here, we demonstrate that Nop53, a late‐acting factor for 60S ribosomal subunit maturation, is crucial for the pathogen's development and virulence. BcNop53 is functionally equivalent to yeast nop53p. Complementation of BcNOP53 completely restored the growth defect of the yeast Δ nop53 mutant. BcNop53 is located in nuclei and disruption of BcNOP53 also dramatically impaired pathogen growth. Deletion of BcNOP53 blocked infection structure formation and abolished virulence of the pathogen, possibly due to reduced production of reactive oxygen species. Moreover, loss of BcNOP53 impaired pathogen conidiation and stress adaptation, altered conidial and sclerotial morphology, retarded conidium and sclerotium germination as well as reduced the activities of cell‐wall degradation‐associated enzymes. Sclerotium production was, however, increased. Complementation with the wild‐type BcNOP53 allele rescued defects found in the Δ Bcnop53 mutant. Our work establishes a systematic elucidation of Nop53 in regulating microbial development and pathogenesis, provides novel insights into ribosomal processes that regulate fungal pathogenesis, and may open up new targets for addressing fungal diseases.

Oxidation state inherited from the magma source and implications for mineralization: Late Jurassic to Early Cretaceous granitoids, Central Lhasa subterrane, Tibet - MingJian Cao; KeZhang Qin; GuangMing Li; Noreen J. Evans; Brent I.A. McInnes; JinXiang Li; JunXing Zhao (Mineralium Deposita, 2018)

Characteristics of Ordovician paleokarst inclusions and their implications for paleoenvironmental and geological history in Halahatang area of northern Tarim Basin - Zhang Qingyu; Qin Fengrui; Liang Bin; Cao Jianwen; DanYong; Li Jingrui; Chen Lixin (Carbonates and Evaporites, 2018)

Development of multifunctional nanoparticles towards applications in non-invasive magnetic resonance imaging and axonal tracing - Yan Du; Yubo Qin; Zizhen Li; Xiuying Yang; Jingchang Zhang; Harrison Westwick; Eve Tsai; Xudong Cao (JBIC Journal of Biological Inorganic Chemistry, 2017)

Facile synthesis of Gd-doped CdTe quantum dots with optimized properties for optical/MR multimodal imaging - Zizhen Li; Ali Dergham; Holly McCulloch; Yubo Qin; Xiuying Yang; Jingchang Zhang; Xudong Cao (JBIC Journal of Biological Inorganic Chemistry, 2017)

Microsatellite records for volume 9, issue 4 - Zhaosheng Cai; Wenxuan Cao; Jie Chen; Jiayin Dai; Ge Ding; Samantha Gray; Jiasheng Hao; Xiayun Jiang; B. B. Li; Yao Li; Z. B. Li; Gang Liu; et al. (Conservation Genetics Resources, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Risk alleles for IgA nephropathy-associated SNPs conferred completely opposite effects to idiopathic membranous nephropathy in Chinese Han - Xiaosong Qin; Chen Wang; Guanting Lu; Mengle Peng; Guixue Cheng; Hongquan Zhu; Yun Cao; Jianhua Liu; Yuzhong Li; Hong Cai; Funing Yang; Yanhong Liu; et al. (Immunologic Research, 2017)

Establishment of a somatic embryo regeneration system and expression analysis of somatic embryogenesis-related genes in Chinese chestnut (Castanea mollissima Blume) - Dan Lu; Wei Wei; Wan Zhou; Linda D. McGuigan; Fei-yang Ji; Xiao Li; Yu Xing; Qing Zhang; Ke-feng Fang; Qing-qin Cao; Ling Qin (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Bacillus zanthoxyli sp. nov., a novel nematicidal bacterium isolated from Chinese red pepper (Zanthoxylum bungeanum Maxim) leaves in China - Ma Li; Cao Yong Hong; Wang Xiao Yan; Zheng Shuai Chao; Yang Cheng Gang; Duo Jin Ling; Zhou Xing Kui; Xi Jia Qin; Zhu Ming Liang; Mo Ming He (Antonie van Leeuwenhoek, 2017)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

Olfactory Dysfunction in Parkinson’s Disease Patients with the LRRK2 G2385R Variant - Ming Cao; Zhu-Qin Gu; Yuan Li; Hui Zhang; Xiao-Juan Dan; Shan-Shan Cen; Da-Wei Li; Piu Chan (Neuroscience Bulletin, 2016)

The Toxicity of Aluminum Chloride on Kidney of Rats - Jianyu Liu; Qin Wang; Xudong Sun; Xu Yang; Cuicui Zhuang; Feibo Xu; Zheng Cao; Yanfei Li (Biological Trace Element Research, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Purification, Chemical Characterization, and Bioactivity of an Extracellular Polysaccharide Produced by the Marine Sponge Endogenous Fungus Alternaria sp. SP-32 - Yin Chen; Wen-Jun Mao; Meng-Xia Yan; Xue Liu; Shu-Yao Wang; Zheng Xia; Bo Xiao; Su-Jian Cao; Bao-Qin Yang; Jie Li (Marine Biotechnology, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Isolation, complete genome sequencing, and phylogenetic analysis of the first Chuzan virus in China - Fang Wang; Jun Lin; Jitao Chang; Yingying Cao; Shaomin Qin; Jianmin Wu; Li Yu (Virus Genes, 2016)

Greenhouse gas emissions, soil quality, and crop productivity from a mono-rice cultivation system as influenced by fallow season straw management - Wei Liu; Saddam Hussain; Lishu Wu; Ziguo Qin; Xiaokun Li; Jianwei Lu; Fahad Khan; Weidong Cao; Mingjian Geng (Environmental Science and Pollution Research, 2016)

Hsp70 plays an important role in high-fat diet induced gestational hyperglycemia in mice - Baoheng Xing; Lili Wang; Qin Li; Yalei Cao; Xiujuan Dong; Jun Liang; Xiaohua Wu (Journal of Physiology and Biochemistry, 2015)

Low-Dose Topical 5-Aminolevulinic Acid Photodynamic Therapy in the Treatment of Different Severity of Acne Vulgaris - Shi-qin Tao; Fei Li; Lei Cao; Ru-shan Xia; Hua Fan; Ying Fan; Hui Sun; Cheng Jing; Li-jia Yang (Cell Biochemistry and Biophysics, 2015)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Putative phage-display epitopes of the porcine epidemic diarrhea virus S1 protein and their anti-viral activity - Liyan Cao; Xuying Ge; Yu Gao; Dante S. Zarlenga; Kexiong Wang; Xunliang Li; Zhaoheng Qin; Xiangping Yin; Jisheng Liu; Xiaofeng Ren; Guangxin Li (Virus Genes, 2015)

Soluble Epoxide Hydrolase Deficiency or Inhibition Attenuates MPTP-Induced Parkinsonism - Xiaocui Qin; Qiaoqi Wu; Lifang Lin; Aimin Sun; Shuhu Liu; Xiaowen Li; Xiong Cao; Tianming Gao; Pengcheng Luo; Xinhong Zhu; Xuemin Wang (Molecular Neurobiology, 2015)

Replacement of fish meal by meat and bone meal in diets for juvenile snakehead Ophiocephalus argus - Hairui Yu; Qin Zhang; Hui Cao; Tong Tong; Guoqiang Huang; Weizhong Li (Fisheries Science, 2015)

Petrogenesis of diabase from accretionary prism in the southern Q iangtang terrane, central T ibet: Evidence from U – P b geochronology, petrochemistry and Sr – Nd – Hf – O isotope characteristics - Jin‐Xiang Li; Ke‐Zhang Qin; Guang‐Ming Li; Jun‐Xing Zhao; Ming‐Jian Cao (Island Arc, 2015)
The B angong– N ujiang suture ( BNS ) between the L hasa and Q iangtang terranes is an important boundary and its petrogenesis is controversial. Diabase from the accretionary prism in the southern Q iangtang terrane yields a zircon U – Pb age of 181.3 ± 1.4 Ma. All the diabases show tholeiitic basalt compositions, gentle enrichment patters of light rare earth elements ( REE ), variable enrichment in incompatible element concentrations (e.g. Th and Rb ), and no anomaly in high field strength elements (e.g. Nb and Ta ), similar to that of enriched mid‐ocean ridge basalt ( E ‐ MORB ). They have relatively homogeneous whole rock Nd (ε Nd (t) = 7.3–9.1) and zircon Hf – O isotopic compositions (ε Hf (t) = 14.8–16.1, and δ 18 O = 4.57–6.12‰), possibly indicating melting of the depleted mantle and no significant crustal contamination during the petrogenesis. The element variations suggest that the diabases were formed by plume–ridge interaction at a mid‐ocean ridge within the B angong– N ujiang ocean.

Ischemic Preconditioning Provides Neuroprotection by Induction of AMP-Activated Protein Kinase-Dependent Autophagy in a Rat Model of Ischemic Stroke - Teng Jiang; Jin-Tai Yu; Xi-Chen Zhu; Qiao-Quan Zhang; Meng-Shan Tan; Lei Cao; Hui-Fu Wang; Jian-Quan Shi; Li Gao; Hao Qin; Ying-Dong Zhang; Lan Tan (Molecular Neurobiology, 2015)

Isolation and characterization of dengue virus serotype 2 from the large dengue outbreak in Guangdong, China in 2014 - Hui Zhao; LingZhai Zhao; Tao Jiang; XiaoFeng Li; Hang Fan; WenXin Hong; Yu Zhang; Qin Zhu; Qing Ye; YiGang Tong; WuChun Cao; FuChun Zhang; et al. (Science China Life Sciences, 2014)

Isoflurane Protects Against Injury Caused by Deprivation of Oxygen and Glucose in Microglia Through Regulation of the Toll-Like Receptor 4 Pathway - Hai-Fei Xiang; Dong-Hang Cao; Yan-Qing Yang; Hui-Qin Wang; Li-Jun Zhu; Bin-Hao Ruan; Jing Du; Ming-Cang Wang (Journal of Molecular Neuroscience, 2014)

Bernoulli-based random undersampling schemes for 2D seismic data regularization - Rui Cai; Qun Zhao; De-Ping She; Li Yang; Hui Cao; Qin-Yong Yang (Applied Geophysics, 2014)

The methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism and tumor risk: evidence from 134 case–control studies - Min Tang; Shang-Qian Wang; Bian-Jiang Liu; Qiang Cao; Bing-Jie Li; Peng-Chao Li; Yong-Fei Li; Chao Qin; Wei Zhang (Molecular Biology Reports, 2014)

Effects of cannabinoid receptor type 2 on endogenous myocardial regeneration by activating cardiac progenitor cells in mouse infarcted heart - YaBin Wang; Sai Ma; Qiang Wang; WenXing Hu; DongJuan Wang; XiuJuan Li; Tao Su; Xing Qin; XiaoTian Zhang; Ke Ma; JiangWei Chen; LiZe Xiong; et al. (Science China Life Sciences, 2014)

Silencing MAP3K1 expression through RNA interference enhances paclitaxel-induced cell cycle arrest in human breast cancer cells - Pinghua Hu; Qin Huang; Zhihua Li; Xiaobo Wu; Qianwen Ouyang; Jun Chen; Yali Cao (Molecular Biology Reports, 2014)

miR-154 inhibits EMT by targeting HMGA2 in prostate cancer cells - Chen Zhu; Jie Li; Gong Cheng; Hai Zhou; Liangjun Tao; Hongzhou Cai; Pu Li; Qiang Cao; Xiaobing Ju; Xiaoxin Meng; Meilin Wang; Zhengdong Zhang; et al. (Molecular and Cellular Biochemistry, 2013)

Microdissection and painting of the Y chromosome in spinach (Spinacia oleracea) - Chuan-liang Deng; Rui-yun Qin; Ying Cao; Jun Gao; Shu-fen Li; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2013)

Population pharmacokinetics of piperacillin/tazobactam in neonates and young infants - Zhiping Li; Yewei Chen; Qin Li; Di Cao; Wenjing Shi; Yun Cao; Dan Wu; Yiqing Zhu; Yi Wang; Chao Chen (European Journal of Clinical Pharmacology, 2013)

Saccharopolyspora dendranthemae sp. nov. a halotolerant endophytic actinomycete isolated from a coastal salt marsh plant in Jiangsu, China - Yue-Ji Zhang; Wen-Di Zhang; Sheng Qin; Guang-Kai Bian; Ke Xing; Yun-Feng Li; Cheng-Liang Cao; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2013)

An L-Type Calcium Channel Agonist, Bay K8644, Extends the Window of Intervention Against Ischemic Neuronal Injury - Hong-hai Hu; Shu-ji Li; Pu Wang; Hua-cheng Yan; Xiong Cao; Feng-qin Hou; Ying-ying Fang; Xin-hong Zhu; Tian-ming Gao (Molecular Neurobiology, 2013)

Beraprost sodium attenuates cigarette smoke extract-induced apoptosis in vascular endothelial cells - Yan Chen; Hong Luo; Naixin Kang; Chaxiang Guan; Yingjiao Long; Jun Cao; Qin Shen; Junli Li; Min Yang; Hong Peng; Ping Chen (Molecular Biology Reports, 2012)

Petrogenesis and thermal history of the Yulong porphyry copper deposit, Eastern Tibet: insights from U-Pb and U-Th/He dating, and zircon Hf isotope and trace element analysis - Jinxiang Li; Kezhang Qin; Guangming Li; Mingjian Cao; Bo Xiao; Lei Chen; Junxing Zhao; Noreen J. Evans; Brent I. A. McInnes (Mineralogy and Petrology, 2012)

Involvement of CtBP2 in LPS-induced microglial activation - Guowei Zhang; Yaohua Yan; Lihua Kang; Qi Cao; Kaifu Ke; Xinmin Wu; Yilu Gao; Qinglei Hang; Chunmiao Li; Lin Zhu; Qin Yuan; Qiyun Wu; et al. (Journal of Molecular Histology, 2012)

Update analysis of studies on the MMP-9 −1562 C>T polymorphism and cancer risk - Li-Feng Zhang; Yuan-Yuan Mi; Qiang Cao; Wei Wang; Chao Qin; Jun-Feng Wei; Yao-Jun Zhou; Yong-Fei Li; Min Tang; Wei-Min Liu; Wei Zhang; Jian-Gang Zou (Molecular Biology Reports, 2012)

Divalent Metal Transporter 1 Expression and Regulation in Human Placenta - Yan-Qin Li; Bin Bai; Xiao-Xiao Cao; Yao-Hui Zhang; Hong Yan; Quan-Qing Zheng; Gui-Hua Zhuang (Biological Trace Element Research, 2012)

RNASEL −1385G/A polymorphism and cancer risk: a meta-analysis based on 21 case–control studies - Li-Feng Zhang; Yuan-Yuan Mi; Chao Qin; Yong Wang; Qiang Cao; Jun-Feng Wei; Yao-Jun Zhou; Ning-Han Feng; Wei Zhang (Molecular Biology Reports, 2011)

Physical and Mechanical Properties of Fine-Grained Soil in the Zhejiang-Fujian Coastal Area, China - Yuan-Qin Xu; Pei-Ying Li; Ping Li; Le-Jun Liu; Cheng-Xiao Cao; Xiu-Li Feng (Marine Georesources & Geotechnology, 2011)

Activated Immune Cells in Parkinson's Disease - Jun-Jun Cao; Kang-Sheng Li; Yan-Qin Shen (Journal of Neuroimmune Pharmacology, 2011)

Expression analysis of Bombyx mori parvo-like virus VD2-ORF1 gene encoding a minor structural protein - Jie Kong; Zhaogyang Hu; Yuanqing He; Guohui Li; Jian Cao; Fenghua Wang; Keping Chen; Qin Yao (Biologia, 2011)

The Non-Structural Protein NS-2 of Bombyx mori Parvo-like Virus is Localized to the Nuclear Membrane - Fenghua Wang; Zhaoyang Hu; Yuanqing He; Guohui Li; Jie Kong; Jian Cao; Keping Chen; Qin Yao (Current Microbiology, 2011)

Pseudonocardia sichuanensis sp. nov., a novel endophytic actinomycete isolated from the root of Jatropha curcas L. - Sheng Qin; Ke Xing; Shi-Min Fei; Qiang Lin; Xiu-Min Chen; Cheng-Liang Cao; Yong Sun; Yun Wang; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2011)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Overexpression of Trpp5 contributes to cell proliferation and apoptosis probably through involving calcium homeostasis - Yan Xiao; Xiaoyan Lv; Ge Cao; Guohui Bian; Jingjing Duan; Jianzhong Ai; Huan Sun; Qingwei Li; Qiutan Yang; Tielin Chen; Danhua Zhao; Ruizhi Tan; et al. (Molecular and Cellular Biochemistry, 2010)

Antioxidative responses related to H2O2 depletion in Hypnum plumaeforme under the combined stress induced by Pb and Ni - Shou-Qin Sun; Ming He; Tong Cao; Yusufujiang Yusuyin; Wei Han; Jin-Ling Li (Environmental Monitoring and Assessment, 2010)

Identification and characterization of a novel capsid protein encoded by Singapore grouper iridovirus ORF038L - Qing Jiao Wan; Jie Gong; Xiao Hong Huang; You Hua Huang; Sheng Zhou; Zheng Liang Ou-Yang; Jian Hao Cao; Li Li Ye; Qi Wei Qin (Archives of Virology, 2010)

Characterization of DUF724 gene family in Arabidopsis thaliana - Xi Cao; Ke-Zhen Yang; Chuan Xia; Xue-Qin Zhang; Li-Qun Chen; De Ye (Plant Molecular Biology, 2010)

Effects of mulch, N fertilizer, and plant density on wheat yield, wheat nitrogen uptake, and residual soil nitrate in a dryland area of China - Yajun Gao; Yun Li; Jianchang Zhang; Wenguo Liu; Zhanping Dang; Weixian Cao; Qin Qiang (Nutrient Cycling in Agroecosystems, 2009)

An improved reverse transcription loop-mediated isothermal amplification assay for sensitive and specific detection of Newcastle disease virus - Qiang Li; Chunyi Xue; Jianping Qin; Qingfeng Zhou; Feng Chen; Yingzuo Bi; Yongchang Cao (Archives of Virology, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

Homocysteine enhances cell proliferation in hepatic myofibroblastic stellate cells - Cheng-Gang Zou; Shun-Yu Gao; Yue-Shui Zhao; Shu-De Li; Xiu-Zhen Cao; Yan Zhang; Ke-Qin Zhang (Journal of Molecular Medicine, 2009)

Overexpression ofGbERF confers alteration of ethylene-responsive gene expression and enhanced resistance toPseudomonas syringae in transgenic tobacco - Jie Qin; Kaijing Zuo; Jingya Zhao; Hua Ling; Youfang Cao; Chengxiang Qiu; Fupeng Li; Xiaofen Sun; Kexuan Tang (Journal of Biosciences, 2006)

Residues of Hexachlorocyclohexane Isomers and Their Distribution Characteristics in Soils in the Tianjin Area, China - Z. M. Gong; F. L. Xu; R. Dawson; J. Cao; W. X. Liu; B. G. Li; W. R. Shen; W. J. Zhang; B. P. Qin; R. Sun; S. Tao (Archives of Environmental Contamination and Toxicology, 2004)

Comparative study on Co2 emissions from different types of alpine meadows during grass exuberance period - Hu Qiwu; Cao Guangmin; Wu Qin; Li Dong; Wang Yuesi (Journal of Geographical Sciences, 2004)